High refractive index silicate and borosilicate glasses
Patent Information
- Application Number
- CN202280038241.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-03
- Filing Date
- 2022-04-04
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-04-04
Smart Images

Figure CN117480135B_ABST
Abstract
Description
[0001] This application claims priority to Dutch Patent Application No. 2028132, filed May 3, 2021, which claims priority to U.S. Provisional Patent Application Serial No. 63 / 170,734, filed April 5, 2021, the contents of which are based and incorporated herein by reference in their entirety. Technical Field
[0002] This disclosure generally relates to borate and borosilicate glasses with high refractive index and low density. Background Technology
[0003] Glass is used in a variety of optical devices, including augmented reality devices, virtual reality devices, mixed reality devices, and eyeglasses. The properties required for this type of glass typically include a high refractive index and low density. Other desired properties may include high transmittance and / or low optical dispersion in the visible and near-ultraviolet (near-UV) ranges of the electromagnetic spectrum. Demanding a combination of these desired properties and the ability to form a glass from a composition with good glass-forming ability can be challenging. For example, generally, as the refractive index of glass increases, its density tends to increase as well. Substances such as TiO2 and Nb2O5 are often added to increase the refractive index of the glass without increasing its density. However, these materials typically absorb blue and UV light, which undesirably reduces the light transmittance of the glass in this spectral region. Generally, attempting to increase the refractive index of glass while maintaining low density without reducing transmittance in the blue and UV regions of the spectrum results in a decrease in the glass-forming ability of the material. For example, crystallization and / or liquid-liquid phase separation can occur during the cooling of the glass melt at industrially acceptable cooling rates. Typically, as the amount of certain substances (e.g., ZrO2, Y2O3, Sc2O3, BeO, etc.) increases, the glass forming ability appears to decrease.
[0004] Depending on the glass-forming agent used, low-density, high-refractive-index glasses typically fall into one of two chemical systems: (a) borosilicate or borosilicate glasses, where SiO2 and / or B2O3 are used as the primary glass-forming agent, and (b) phosphate glasses, where P2O5 is used as the primary glass-forming agent. The use of glasses that rely on other oxides as primary glass-forming agents (GeO2, TeO2, Bi2O3, and V2O5) can be challenging due to cost, glass-forming capability, optical properties, and / or production requirements.
[0005] Phosphate glasses are characterized by high refractive index and low density. However, producing phosphate glasses can be challenging due to the risk of P2O5 volatilization from the melt and / or platinum incompatibility. Furthermore, phosphate glasses are typically highly colored and may require additional bleaching steps to provide glass with the desired transmission properties. In addition, phosphate glasses exhibiting high refractive indices tend to have increased optical dispersion.
[0006] Generally speaking, borosilicate and borosilicate glasses are easier to produce and can exhibit high transmittance without a bleaching step. However, compared to phosphate glasses, borosilicate and borosilicate glasses typically exhibit increased density with increasing refractive index.
[0007] Based on these considerations, there is a demand for borate and borosilicate glasses with high refractive index, low density, and high blue light transmittance. Summary of the Invention
[0008] According to embodiments of this disclosure, the glass comprises multiple components, and the component composition of the glass includes: greater than or equal to 0.5 mol% and less than or equal to 29.0 mol% B2O3, greater than or equal to 0.0 mol% and less than or equal to 25.2 mol% TiO2, greater than or equal to 0.0 mol% and less than or equal to 20.0 mol% Bi2O3, greater than or equal to 0.0 mol% and less than or equal to 20.0 mol% TeO2, greater than or equal to 0.0 mol% and less than or equal to 15.0 mol% P2O5, greater than or equal to 0.0 mol% and less than or equal to... The following concentrations are present: 10.5 mol% Nb₂O₅, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% Al₂O₃, greater than or equal to 0.0 mol% and less than or equal to 5.0 mol% MoO₃, greater than or equal to 0.0 mol% and less than or equal to 4.0 mol% V₂O₅, greater than or equal to 0.0 mol% and less than or equal to 2.5 mol% GeO₂, greater than or equal to 0.0 mol% and less than or equal to 2.5 mol% ZnO, greater than or equal to 0.0 mol% and less than or equal to 1.0 mol% Ta₂O₅, and greater than or equal to 95.0 mol% R. m O n ≥0.0 mol% and ≤29.0 mol% RE m O n The composition of the glass is greater than or equal to 10.0 mol% SiO2+B2O3+P2O5, less than or equal to 34.0 mol% SiO2+B2O3, greater than or equal to 0.3 mol% CaO+SrO+BaO+Y2O3, and greater than or equal to 0.0 mol% and less than or equal to 25.0 mol% R2O+RO, wherein the composition satisfies the following condition: Y2O3-Gd2O3 [mol%] ≥ -2.0, and the glass satisfies the following condition: 4.0 ≤ Pd ≤6.0 and P n -(1.207+0.155*P d )>0.000, where P n It is the refractive index parameter, calculated as a mole percent of the components in the glass composition according to the following equation (I):
[0009] P n =1.844+0.0054162*La2O3+0.0031113*TiO2-0.004212*B2O3-0.0035692*SiO2+0.0027887*ZrO2+0.0078026* Nb2O5-0.00012928*CaO+0.00076566*BaO+0.0043601*Y2O3+0.00067408*ZnO+0.0068029*Gd2O3-0.0025106*N a2O+0.0039937*WO3-0.0043208*Al2O3-0.0011666*Li2O+0.0051727*PbO+0.012958*Bi2O3-0.0018753*GeO2- 0.0014084*TeO2+0.0086647*Er2O3+0.0097345*Yb2O3-0.0038734*K2O-0.00041776*SrO-0.0017294*MgO, (I)
[0010] P d It is a density parameter, calculated as the mole percent of the components in the glass composition according to the following equation (II):
[0011] P d =4.276+0.058714*La2O3-0.0077783*TiO2-0.023741*B2O3-0.018272*SiO2+0.010913*ZrO2-0.00 14478*CaO+0.023857*BaO+0.033560*Y2O3+0.010174*ZnO+0.082094*Gd2O3-0.008237*Na2O+0.03 5497*WO3-0.031171*Al2O3-0.0080004*Li2O+0.051830*PbO+0.10437*Bi2O3-0.012816*GeO2-0.0 065609*TeO2+0.10060*Er2O3+0.10637*Yb2O3-0.017097*K2O+0.009821*SrO-0.0037906*MgO, (II)
[0012] In the formula, R m O n It is the sum of all oxides, RE m O n R₂O is the sum of rare earth metal oxides, R₂O is the sum of monovalent metal oxides, RO is the sum of divalent metal oxides, and the asterisk (*) represents the multiplication sign.
[0013] According to another embodiment of this disclosure, the glass comprises multiple components, and the composition of the glass includes: greater than or equal to 1.0 mol% and less than or equal to 40.0 mol% TiO2, greater than or equal to 1.0 mol% and less than or equal to 40.0 mol% B2O3, greater than or equal to 0.0 mol% and less than or equal to 35.0 mol% SiO2, greater than or equal to 0.0 mol% and less than or equal to 30.0 mol% La2O3, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% ZrO2, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% GeO2, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% Al2O3, and greater than or equal to 0 mol% and less than or equal to 6.75 mol% N. b2O5, greater than or equal to 0.0 mol% and less than or equal to 6.7 mol%; Y2O3, greater than or equal to 0.0 mol% and less than or equal to 25.0 mol%; RO, greater than or equal to 0.0 mol% and less than or equal to 25.0 mol%; R2O, greater than or equal to 45.3 mol%; La2O3+Y2O3+Gd2O3+TiO2, greater than or equal to 12.1 mol%; Nb2O5+ZrO2, and optionally containing one or more components selected from the group consisting of Bi2O3, Er2O3, Nd2O3, WO3, and Yb2O3, wherein the composition satisfies the following conditions: SiO2+B2O3-TiO2 [mol%] ≥ 7.05 and B2O3-SiO2 [mol%] ≤ 7.0, and the glass satisfies the following condition: P ref -(0.196+0.0016*(TiO2-La2O3))>0.000, where P ref It is the refraction parameter, calculated as the molar percentage of the components in the glass composition according to the following equation (III):
[0014] P ref=0.201656+0.00018225*B2O3-0.0010873*BaO-0.0024853*Bi2O3-0.0030326* Er2O3-0.0018856*Gd2O3-0.0017563*La2O3-0.0002505*Na2O+0.0017526*Nb2 O5-0.0025472*Nd2O3-0.0016439*PbO+0.000050096*SiO2+0.0011794*TiO2-0 .00072112*WO3-0.00079167*Y2O3-0.0031015*Yb2O3-0.00034209*ZnO, (III)
[0015] In the formula, RO is the sum of divalent metal oxides, R2O is the sum of monovalent metal oxides, and the symbol (*) represents the multiplication sign.
[0016] According to one or more embodiments of this disclosure, the glass comprises a variety of components, the composition of which includes: greater than or equal to 1.0 mol% and less than or equal to 40.0 mol% TiO2, greater than or equal to 1.0 mol% and less than or equal to 40.0 mol% B2O3, greater than or equal to 0.0 mol% and less than or equal to 35.0 mol% SiO2, greater than or equal to 0.0 mol% and less than or equal to 30.0 mol% La2O3, greater than or equal to 0.0 mol% and less than or equal to 20.0 mol% CaO, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% ZrO2, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% GeO2, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% Al2O3, greater than or equal to 0 mol% and less than or equal to 6.75 mol% Nb2O5, greater than or equal to 0.0 mol% and less than or equal to... 5.5 mol% BaO, greater than or equal to 0.0 mol% and less than or equal to 4.6 mol% Y₂O₃, greater than or equal to 0.0 mol% and less than or equal to 3.5 mol% ZnO, greater than or equal to 0.0 mol% and less than or equal to 1.0 mol% WO₃, greater than or equal to 0.0 mol% and less than or equal to 25.0 mol% RO, greater than or equal to 0.0 mol% and less than or equal to 25.0 mol% R₂O, greater than or equal to 45.3 mol% The glass comprises %La₂O₃+Yb₂O₃+Y₂O₃+Gd₂O₃+TiO₂, greater than or equal to 11.0 mol% Nb₂O₅+ZrO₂, and optionally contains one or more components selected from the group consisting of Bi₂O₃, Er₂O₃, and Nd₂O₃, wherein the composition satisfies the following conditions: TiO₂-B₂O₃[mol%]≥-6.0 and TiO₂-La₂O₃[mol%]≤5.0, and the glass satisfies the following condition: Pref -(0.199+0.0025*(TiO2-La2O3))>0.000, where P ref It is the refraction parameter, calculated as the molar percentage of the components in the glass composition according to the following equation (III):
[0017] P ref =0.201656+0.00018225*B2O3-0.0010873*BaO-0.0024853*Bi2O3-0.0030326* Er2O3-0.0018856*Gd2O3-0.0017563*La2O3-0.0002505*Na2O+0.0017526*Nb2 O5-0.0025472*Nd2O3-0.0016439*PbO+0.000050096*SiO2+0.0011794*TiO2-0 .00072112*WO3-0.00079167*Y2O3-0.0031015*Yb2O3-0.00034209*ZnO, (III)
[0018] In the formula, RO is the sum of divalent metal oxides, R2O is the sum of monovalent metal oxides, and the symbol (*) represents the multiplication sign.
[0019] Those skilled in the art will understand and appreciate these and other aspects, objects and features of this disclosure by studying the following description, claims and drawings. Attached Figure Description
[0020] Figure 1 The refractive index n of some comparative glass and some exemplary glass according to embodiments of this disclosure is shown. d The refractive index parameter P calculated by equation (I) n A diagram showing the relationships between them.
[0021] Figure 2 The density d at room temperature is shown for some comparative glass and some exemplary glass according to embodiments of this disclosure. RT The density parameter P calculated by equation (II) d A diagram showing the relationships between them.
[0022] Figure 3 The refractive power (n) of some comparative glass and some exemplary glass according to embodiments of this disclosure is shown. d -1) / d RT The refractive power parameter P calculated by equation (III) ref A diagram showing the relationships between them.
[0023] Figure 4 These are exemplary cooling scheme diagrams of some exemplary glasses according to “15-minute test” conditions and “2.5-minute test” conditions, implemented according to embodiments of this disclosure.
[0024] Figure 5 The density parameter P, calculated according to Equation (II), is shown for some comparative glass and some exemplary glass according to embodiments of this disclosure. d The refractive index parameter P calculated according to equation (I) n A diagram showing the relationships between them.
[0025] Figure 6 The density d at room temperature is shown for some comparative glass and some exemplary glass according to embodiments of this disclosure. RT The refractive index n at 587.56 nm d A diagram showing the relationships between them.
[0026] Figure 7 The difference in TiO2-La2O3 between some comparative glass samples and some exemplary glass samples according to embodiments of this disclosure is shown, along with the refractive power parameter P calculated by equation (III). ref A diagram showing the relationships between them.
[0027] Figure 8 The difference between TiO2 and La2O3 and the ratio of refractive index to density (“refractive power”) are shown for some comparative glasses and some exemplary glasses according to embodiments of this disclosure. d -1) / d RT A diagram showing the relationships between them.
[0028] Figure 9 The difference in TiO2-La2O3 between some comparative glass samples and some exemplary glass samples according to embodiments of this disclosure is shown, along with the refractive power parameter P calculated by equation (III). ref A diagram showing the relationships between them.
[0029] Figure 10 The difference between TiO2 and La2O3 and the ratio of refractive index to density (“refractive power”) are shown for some comparative glasses and some exemplary glasses according to embodiments of this disclosure. d -1) / d RT A diagram showing the relationships between them. Detailed Implementation
[0030] In the following detailed description, exemplary embodiments illustrating specific details are given for illustrative purposes and not for limitation, in order to provide a full understanding of the various principles of this disclosure. However, it will be apparent to those skilled in the art that this disclosure may be practiced in other ways than those detailed herein, upon benefiting from this specification. Furthermore, descriptions of well-known devices, methods, and materials may have been omitted so as not to obscure the description of the various principles of the invention. Finally, wherever applicable, the same reference numerals denote the same elements.
[0031] Unless otherwise stated, it is not intended to interpret any method described herein as requiring its steps to be performed in a specific order. Therefore, when a method claim does not actually state that its steps follow a certain order, or does not specifically indicate in the claims or description that the steps are limited to a specific order, it is not intended to imply any particular order. This also applies to any possible unstated basis for interpretation, including but not limited to: the logic regarding the setup of steps or operational procedures; the general meaning derived from grammatical structure or punctuation; and the number or type of embodiments described in the specification.
[0032] As used herein, the term "and / or" when used to list two or more items means that any one of the listed items may be used alone, or any combination of two or more of the listed items may be used. For example, if a composition is described as containing components A, B, and / or C, the composition may contain only A; only B; only C; a combination of A and B; a combination of A and C; a combination of B and C; or a combination of A, B, and C.
[0033] Those skilled in the art, as well as those who utilize and use this disclosure, will make improvements to it. Therefore, it is to be understood that the embodiments shown in the accompanying drawings and described above are merely illustrative and not intended to limit the scope of this disclosure, which is defined by the appended claims and, in accordance with the principles of patent law, is to include the doctrine of equivalents.
[0034] As used herein, the term "about" indicates that a quantity, size, formulation, parameter, and other variable and characteristic is not, and does not need to be, exact, but may be approximate and / or larger or smaller as required, reflecting tolerances, conversion factors, rounding and measurement errors, and other factors known to those skilled in the art. When the term "about" is used to describe a value or endpoint of a range, it should be understood that this disclosure includes the specific value or endpoint referenced. Whether or not the endpoints of a numerical value or range in this specification are stated as "about," the endpoints are intended to include both implementations: one modified with "about" and one not modified with "about." It will also be understood that each endpoint value of a range is meaningful both in relation to and unrelated to another endpoint value.
[0035] The term “formed from…” can indicate one or more of the following: including, substantially composed of, or composed of. For example, a component formed from a particular material may include, substantially composed of, or be composed of that particular material.
[0036] In this document, the terms “free from” and “substantially free from” are used interchangeably, referring to the absence of an amount of a particular component in the glass composition that has not been intentionally added to the glass composition and / or the absence of that particular component. It should be understood that the glass composition may contain trace amounts of a particular constituent component as a contaminant or in an indeterminate amount of less than 0.10 mol%.
[0037] As used herein, when describing a particular constituent component in a glass composition, the term "uncertain" refers to a constituent component that is not intentionally added to the glass composition and is present in an amount of less than 0.10 mol%. Uncertain components may be unintentionally added to the glass composition as impurities in another constituent component and / or through migration of uncertain components into the composition during the processing of the glass composition.
[0038] Unless otherwise stated, the term "glass" is used to refer to glass made from the glass compositions disclosed herein.
[0039] When used in any equation in this paper, the symbol "*" represents a multiplication sign.
[0040] The term “glass forming agent” is used herein to refer to a component that, when present alone in a glass composition (i.e., in the absence of other components, except in indefinite amounts), is capable of forming glass when the melt is cooled at a rate not exceeding about 200°C / min to about 300°C / min.
[0041] As used herein, the term "modifier" refers to an oxide of a monovalent or divalent metal, namely R₂O or RO, where "R" represents a cation. Modifiers can be added to glass compositions to alter the atomic structure of the melt and the resulting glass. In some embodiments, the modifier can alter the coordination number of cations present in the glass forming agent (e.g., boron in B₂O₃), which can lead to the formation of a more polymeric atomic network and, as a result, provide better glass forming.
[0042] As used herein, the term "RO" refers to the total content of divalent metal oxides, the term "R2O" refers to the total content of monovalent metal oxides, and the term "Alk2O" refers to the total content of alkali metal oxides. The term R2O encompasses alkali metal oxides (Alk2O) as well as other monovalent metal oxides, such as Ag2O, Tl2O, and Hg2O. As discussed below, in this disclosure, rare earth metal oxides are expressed with their standard formula (RE2O3), wherein the rare earth metal oxide has a redox state of "+3", and therefore are not included in the terms RO or R2O.
[0043] As used herein, the term "rare earth metal" refers to the metals listed in the lanthanide series of the IUPAC periodic table, plus yttrium and scandium. As used herein, the term "rare earth metal oxide" is used to describe oxides of rare earth metals in different redox states, such as "+3" for lanthanum in La₂O₃, "+4" for cerium in CeO₂, and "+2" for europium in EuO, etc. Generally, the redox state of rare earth metals in oxide glasses can be altered, and specifically, the redox state may change during melting, depending on the batch composition and / or the redox conditions in the furnace where the glass is melted and / or heat-treated (e.g., annealed). Unless otherwise stated, rare earth metal oxides herein are expressed in their standard form, where the rare earth metal oxide has a redox state of "+3". Therefore, when a rare earth metal with a redox state other than "+3" is added to a glass composition batch, the glass composition is recalculated by adding or subtracting some oxygen to maintain the stoichiometry. For example, when CeO2 (cerium in the "+4" redox state) is used as a batch component, the resulting batch composition is recalculated as if 2 moles of CeO2 were equivalent to 1 mole of Ce2O3, and the resulting batch composition presents Ce2O3. As used herein, the term "RE" refers to... m O n The term “RE2O3” is used to refer to the total content of rare earth metal oxides in all redox states present in the ingredient composition, and the term “RE2O3” is used to refer to the total content of rare earth metal oxides in the ingredient composition when recalculated in the “+3” redox state. In this document, the term “RE2O3” is also defined as “trivalent equivalent”.
[0044] Unless otherwise stated, all compositions are expressed as mole percentages (mol%) of the ingredients. Therefore, references to “composition” or “glass composition” refer to the composition in mole percent of the ingredients. Those skilled in the art will understand that various melt components (e.g., fluorine, alkali metals, boron, etc.) may undergo different levels of volatility during melting (e.g., as a function of vapor pressure, melting time, and / or melting temperature). Thus, the term “about” associated with such constituent components is intended to include values that, when measured in the final article, differ from the composition of the as-batched composition provided herein by within about 0.2 mol%. In view of the foregoing, substantial compositional equivalence between the final article and the as-batched composition is contemplated. In some embodiments, when indicated, the composition may be expressed as a percentage of the ingredients by weight (wt%) of the oxides.
[0045] The oxides and other constituent components of glass are referred to as "components". Expressions of components using the mathematical symbols "+" and "-" refer to the sum and difference of the components in the composition, expressed as mol%. For example, the expression "SiO2 + GeO2" or "SiO2 + GeO2 [mol%]" refers to the sum of components SiO2 and GeO2 in the composition, expressed as mol%. In another example, the expression "B2O3 + SiO2 - P2O5" or "B2O3 + SiO2 - P2O5 [mol%]" refers to the sum of components B2O3 and SiO2 minus component P2O5 in the composition, expressed as mol%. If a quantifier precedes the expression, the quantifier refers to the total amount of the components listed in the expression. For example, the statement "4.8 mol% SiO2 + GeO2" means that the combined amount of SiO2 and GeO2 in the ingredient composition is 4.8 mol%, while the statement "less than or equal to 4.8 mol% SiO2 + GeO2" means that the combined amount of SiO2 and GeO2 in the ingredient composition is less than or equal to 4.8 mol%.
[0046] When fluorine or other halogens (chlorine, bromine, and / or iodine) are added to or present in oxide glass, the molecular representation of the resulting ingredient composition can be expressed in different ways. In this disclosure, the halogen content (when present) of the component is expressed as an atomic percentage (atomic %), which is determined by multiplying the fraction of halogens in the sum of all atoms in the ingredient composition by a factor of 100.
[0047] In this disclosure, the following method is used to represent fluorine-containing compositions and concentration ranges. The concentration limits for all oxides presented (e.g., SiO2, B2O3, Na2O, etc.) are based on the following assumptions: the corresponding cations (e.g., silicon [SiO2], B2O3, Na2O, etc.) are based on the following assumptions: 4+ ], Boron [B 3+ ], sodium [Na+ The halogens (such as fluorine, silicon fluoride, and fluorine) initially exist in the form of their corresponding oxides. When fluorine is present as the sole halogen, for the purpose of calculating the component concentration of the formulation, a portion of the oxygen in the oxide is equivalently replaced by fluorine (i.e., one oxygen atom is replaced by two fluorine atoms). It is assumed that the fluorine is present in the form of silicon fluoride (SiF4); therefore, the sum of all oxides and SiF4 is assumed to be 100 mol% or 100 wt% in all compositions. Similar treatment is used for other halogens as the sole halogen or combinations of halogens.
[0048] The density values of the glass recorded in this article are obtained using measurements with an error of 0.001 g / cm³. 3 The Archimedes method was used to measure the concentration in water at room temperature, with units of g / cm³. 3 As used in this paper, density measurements at room temperature (defined as d) RT This refers to measurements taken at 20°C or 25°C, and includes measurements obtained at temperatures ranging from 20°C to 25°C. It should be understood that room temperature may vary between about 20°C and about 25°C; however, for the purposes of this disclosure, density changes within the temperature range of 20°C to 25°C are expected to be less than 0.001 g / cm³. 3 The error is negligible and therefore is not expected to affect the room temperature density measurements recorded in this paper.
[0049] As used in this article, the term "refractive power" refers to the refractive power as a measure of the ratio (n... d -1) / d RT The relationship between refractive index and density is given by the formula, where the refractive index n is measured at 587.56 nm. d And the density d was measured at room temperature. RT The unit is g / cm³ 3 。(n d -1) / d RT The ratio or refractive power can characterize the refractive index n. d With density d RT The relationship between these two values is as follows: the higher the refractive power value, the higher the refractive index for a given density.
[0050] As used herein, good glass formability refers to the melt's resistance to devitrification as it cools. Glass formability can be measured by determining the critical cooling rate of the melt. As used herein, the term "critical cooling rate" or "v" is used... cr The critical cooling rate refers to the minimum cooling rate at which a melt of a given composition can form glass without visually visible crystals under an optical microscope at magnification of 100x to 500x. The critical cooling rate can be used to measure the glass-forming ability of a composition, that is, the ability of a melt of a given glass composition to form glass upon cooling. Generally speaking, the lower the critical cooling rate, the better the glass-forming ability.
[0051] The term "liquidline temperature" in this document refers to the temperature above which the glass composition is completely liquid and free of crystallization of glass constituent components. The liquidline temperature values recorded herein are obtained by means of DSC or by isothermal holding of the sample wrapped in platinum foil. For samples measured using DSC, the powdered sample was heated to 1250°C at a rate of 10 K / min. The endpoint corresponding to the endothermic event of crystal melting is considered the liquidline temperature. For the second technique (isothermal holding), a glass block (approximately 1 cm²) was used. 3 The glass was wrapped in platinum foil (to prevent evaporation) and placed in a furnace at a given temperature for 17 hours. The glass block was then examined using an optical microscope to inspect the crystals.
[0052] Unless otherwise stated, the refractive index values recorded herein were measured at room temperature (approximately 25°C). The refractive index values of the glass samples were measured using a Metricon Model 2010 prism-coupled refractometer with an error of approximately ±0.0002. Using the Metricon, the refractive index of the glass samples was measured at two or more wavelengths, approximately 406 nm, 473 nm, 532 nm, 633 nm, 828 nm, and 1064 nm. The measured correlations characterized the dispersion, which was then fitted using either Cauchy's law equation or the Sellmeier equation to calculate the refractive index of the sample at a given wavelength of interest between the measurement wavelengths. The term "refractive index n" as used herein is... d "or "n d "Refractive index n" refers to the refractive index calculated at a wavelength of 587.56 nm as described above, which corresponds to the wavelength of the helium d-line. As used herein, the term "refractive index n" is... C "or "n C "Refractive index n" refers to the refractive index calculated at a wavelength of 656.3 nm as described above. As used herein, the term "refractive index n" is... F "or "n F "Refractive index n" refers to the refractive index calculated at a wavelength of 486.1 nm as described above. As used herein, the term "refractive index n" is... g "or "n g "Refers to the refractive index calculated at a wavelength of 435.8 nm, as mentioned above."
[0053] Unless otherwise stated, as used herein, the term "high refractive index" or "high refractive index" refers to a glass with a refractive index value greater than or equal to 1.80. In the illustrated embodiments, the term "high refractive index" or "high refractive index" refers to a glass with a refractive index value greater than or equal to 1.85, greater than or equal to 1.90, greater than or equal to 1.95, or greater than or equal to 2.00.
[0054] The terms "dispersion" and "optical dispersion" are used interchangeably to describe the difference or ratio of refractive indices of a glass sample at a predetermined wavelength. One numerical measurement of optical dispersion documented in this paper is the Abbe number, which can be calculated using the following equation: ν x =(n x –1) / (n F –n C In the formula, "x" in this disclosure refers to one of the commonly used wavelengths (e.g., ν). d 587.56nm [d-line] or ν D (589.3nm [D line]), n x It is the refractive index at this wavelength (e.g., n). d Corresponding to ν d , and n D Corresponding to ν D ), and n F and n C These are the refractive indices at wavelengths of 486.1 nm (F line) and 656.3 nm (C line), respectively. d and ν D The numerical differences are very subtle, mostly within ±0.1% to ±0.2%. A higher Abbe number corresponds to a lower optical dispersion.
[0055] The Abbe number corresponding to "high dispersion" or "low dispersion" can vary depending on the refractive index used to calculate the Abbe number. In some cases, the Abbe number corresponding to "low dispersion" for high-refractive-index glass may be lower than the corresponding Abbe number for low-refractive-index glass. In other words, as the calculated refractive index increases, the Abbe number corresponding to low dispersion decreases. The same applies to "high dispersion."
[0056] As used herein, the term "α" or "α" refers to... 20-300 "α" refers to the linear coefficient of thermal expansion (CTE) of a glass composition over a temperature range from 20°C to 300°C. This property is measured using a horizontal dilatometer (push-rod dilatometer) according to ASTM E228-11. The numerical measurement of α is the linear average value over a specified temperature range ΔT (e.g., 20°C to 300°C), expressed as α = ΔL / L0ΔT, where L0 is the linear dimension of the sample at or near the measurement range, and L is the change in linear dimension (ΔL) over the measurement temperature range ΔT.
[0057] Young's modulus E and Poisson's ratio μ were measured using resonant ultrasonic spectroscopy with a Quasar RUSpec 4000 purchased from the Magnaflux Division of ITW Indiana Private Limited.
[0058] The glass transition temperature (Tg) was measured by differential scanning calorimetry (DSC) at a heating rate of 10 K / min after cooling to room temperature in air.
[0059] As used herein, the term "annealing point" refers to the temperature determined according to ASTM C598-93 (2013), at which the glass viscosity of a given glass composition is approximately 10. 13.2 moor.
[0060] The glass composition may contain boron oxide (B₂O₃). According to some embodiments of this disclosure, boron oxide can act as a glass forming agent. As a glass forming agent, B₂O₃ can help increase the liquidus viscosity (viscosity at the liquidus temperature) and thus protect the glass composition from crystallization. However, adding B₂O₃ to the glass composition may cause liquid-liquid phase separation, which may result in devitrification and / or reduced transmittance of the resulting glass. Furthermore, adding B₂O₃ to high-refractive-index glasses reduces the refractive index. Therefore, the amount of boron oxide in the glass of this disclosure is limited, or the glass may be substantially free of B₂O₃. In embodiments, the amount of boron oxide (B₂O₃) contained in the glass composition may be greater than or equal to 0.5 mol% to less than or equal to 40.0 mol%, and all ranges and subranges between the above values. In some embodiments, the amount of B2O3 contained in the glass composition may be: greater than or equal to 0.5 mol%, greater than or equal to 1.0 mol%, greater than or equal to 5.0 mol%, greater than or equal to 15.0 mol%, greater than or equal to 16.0 mol%, greater than or equal to 16.4 mol%, greater than or equal to 16.9 mol%, greater than or equal to 18.4 mol%, greater than or equal to 20.0 mol%, greater than or equal to 25.0 mol%, greater than or equal to 30.0 mol%, or greater than or equal to 35.0 mol%. In some other embodiments, the amount of B2O3 contained in the glass composition may be: less than or equal to 40.0 mol%, less than or equal to 35.0 mol%, less than or equal to 30.0 mol%, less than or equal to 29.0 mol%, less than or equal to 25.0 mol%, less than or equal to 22.5 mol%, less than or equal to 21.0 mol%, less than or equal to 20.4 mol%, less than or equal to 20.0 mol%, or less than or equal to 5.0 mol%.In some further embodiments, the amount of B2O3 contained in the glass composition may be: greater than or equal to 0.5 mol% and less than or equal to 29.0 mol%, greater than or equal to 1.0 mol% and less than or equal to 40.0 mol%, greater than or equal to 15.0 mol% and less than or equal to 22.5 mol%, greater than or equal to 16.0 mol% and less than or equal to 21.0 mol%, greater than or equal to 16.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 16.4 mol% and less than or equal to 20.4 mol%, greater than or equal to 16.9 mol% and less than or equal to 20.4 mol%, and greater than or equal to 18.38 mol%. % and less than or equal to 20.37 mol%, greater than or equal to 0.5 mol% and less than or equal to 40.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 40.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 20.0 mol% and less than or equal to 20.4 mol%, greater than or equal to 20.4 mol% and less than or equal to 40.0 mol%, greater than or equal to 20.4 mol% and less than or equal to 21.0 mol%, greater than or equal to 21.0 mol% and less than or equal to 22.5 mol%, greater than or equal to 22.5 mol% and less than or equal to 25.0 mol%.
[0061] The glass composition may contain silica (SiO2). Silica can act as an additional glass-forming agent. Silica, along with B2O3, can help increase the liquidus viscosity and thus protect the glass composition from crystallization. However, adding SiO2 to the glass composition may cause liquid-liquid phase separation, which may result in devitrification and / or reduced transmittance of the resulting glass. Furthermore, SiO2 is a low refractive index component and makes it difficult to achieve high refractive index glasses. Therefore, the SiO2 content in the embodiments of this disclosure is limited, or the glass may be substantially free of SiO2. In embodiments, the amount of silica (SiO2) contained in the glass composition may be greater than or equal to 0.0 mol% to less than or equal to 35.0 mol%, and all ranges and subranges between the above values. In some embodiments, the amount of SiO2 contained in the glass composition may be: greater than or equal to 0.0 mol%, greater than or equal to 5.0 mol%, greater than or equal to 7.5 mol%, greater than or equal to 10.0 mol%, greater than or equal to 11.0 mol%, greater than or equal to 20.0 mol%, greater than or equal to 25.0 mol%, or greater than or equal to 30.0 mol%. In some other embodiments, the amount of SiO2 contained in the glass composition may be: less than or equal to 35.0 mol%, less than or equal to 34.0 mol%, less than or equal to 30.0 mol%, less than or equal to 25.0 mol%, less than or equal to 20.0 mol%, less than or equal to 17.5 mol%, less than or equal to 16.5 mol%, less than or equal to 15.0 mol%, or less than or equal to 5.0 mol%. In some further embodiments, the amount of SiO2 contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 35.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 7.5 mol% and less than or equal to 20.0 mol%, greater than or equal to 10.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 10.0 mol% and less than or equal to 17.5 mol%, greater than or equal to 11.0 mol% and less than or equal to 16.5 mol%, greater than or equal to 11.16 mol% and less than or equal to 15.22 mol%, greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 15.0 mol% and less than or equal to 16.5 mol%, greater than or equal to 16.5 mol% and less than or equal to 17.5 mol%, and greater than or equal to 17.5 mol% and less than or equal to 20.0 mol%.
[0062] The glass composition may contain phosphorus oxide (P2O5). The glass compositions described herein may contain phosphorus oxide (P2O5) as an additional glass-forming agent. A larger amount of P2O5 results in a greater increase in melt viscosity at the same given temperature, which protects the melt from crystallization upon cooling and thus allows for better glass-forming ability (i.e., a lower critical cooling rate). However, the addition of P2O5 to the glass composition significantly reduces the refractive index, making it more difficult to achieve the desired high refractive index. Furthermore, in some cases, this may stimulate liquid-liquid phase separation, which can lead to crystallization of the melt forming the glass upon cooling and / or a loss of transmittance. Additionally, P2O5 may increase the liquidus temperature for a given composition due to the low solubility of the refractory phosphate phase at relevant temperatures. Therefore, the P2O5 content is limited in high-refractive-index glasses, or the glass may be P2O5-free. In embodiments, the amount of phosphorus oxide (P2O5) contained in the glass composition can be greater than or equal to 0.0 mol% to less than or equal to 15.0 mol%, and all ranges and subranges between the above values. In some embodiments, the amount of P2O5 contained in the glass composition can be: greater than or equal to 0.0 mol%, greater than or equal to 5.0 mol%, greater than or equal to 9.0 mol%, greater than or equal to 10.0 mol%, greater than or equal to 11.0 mol%, or greater than or equal to 13.0 mol%. In some other embodiments, the amount of P2O5 contained in the glass composition can be: less than or equal to 15.0 mol%, less than or equal to 13.0 mol%, less than or equal to 11.0 mol%, less than or equal to 10.0 mol%, less than or equal to 9.0 mol%, or less than or equal to 5.0 mol%. In some further embodiments, the amount of P2O5 contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 15.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 15.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 9.0 mol%, greater than or equal to 9.0 mol% and less than or equal to 15.0 mol%, greater than or equal to 9.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 10.0 mol% and less than or equal to 15.0 mol%, greater than or equal to 10.0 mol% and less than or equal to 11.0 mol%, greater than or equal to 11.0 mol% and less than or equal to 15.0 mol%, greater than or equal to 11.0 mol% and less than or equal to 13.0 mol%.
[0063] The glass composition may contain germanium oxide (GeO2). Germanium oxide (GeO2) provides an excellent refractive index to density ratio and does not reduce transmittance. However, germanium oxide is expensive, and therefore it may make the glass composition uneconomical. Therefore, the germanium oxide content should be limited, or the glass composition may be GeO2-free, or substantially GeO2-free. In embodiments, the amount of germanium oxide (GeO2) contained in the glass composition may be greater than or equal to 0.0 mol% to less than or equal to 10.0 mol%, and all ranges and subranges between these values. In some embodiments, the amount of GeO2 contained in the glass composition may be: greater than or equal to 0.0 mol%, greater than or equal to 5.0 mol%, greater than or equal to 7.0 mol%, greater than or equal to 8.0 mol%, or greater than or equal to 9.0 mol%. In some other embodiments, the amount of GeO2 contained in the glass composition may be: less than or equal to 10.0 mol%, less than or equal to 9.0 mol%, less than or equal to 8.0 mol%, less than or equal to 7.0 mol%, less than or equal to 5.0 mol%, less than or equal to 2.5 mol%, or less than or equal to 0.5 mol%. In some further embodiments, the amount of GeO2 contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 2.5 mol%, greater than or equal to 0.0 mol% and less than or equal to 0.5 mol%, greater than or equal to 0.5 mol% and less than or equal to 10.0 mol%, greater than or equal to 0.5 mol% and less than or equal to 2.5 mol%, greater than or equal to 2.5 mol% and less than or equal to 10.0 mol%, greater than or equal to 2.5 mol% and less than or equal to 5.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 7.0 mol%.
[0064] In some embodiments, the total amount of all oxides contained in the glass composition, R m O n The amount can be greater than or equal to 95.0 mol%.
[0065] In some embodiments, the glass composition contains rare earth metal oxides RE m O n The amount can be: greater than or equal to 0.0 mol%, greater than or equal to 10.0 mol%, or greater than or equal to 20.0 mol%. In some other embodiments, the glass composition contains rare earth metal oxides RE m O n The amount can be: less than or equal to 29.0 mol%, less than or equal to 20.0 mol%, or less than or equal to 10.0 mol%. In some further embodiments, the glass composition contains REm O n The amount can be: greater than or equal to 0.0 mol% and less than or equal to 29.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 20.0 mol%, or greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 10.0 mol% and less than or equal to 29.0 mol%, or greater than or equal to 10.0 mol% and less than or equal to 20.0 mol%.
[0066] The glass composition may contain lanthanum oxide (La₂O₃). Lanthanum oxide is one of the cheapest oxides that provides a high refractive index without significant loss of transmittance in the visible light range. Furthermore, the addition of La₂O₃ can reduce the risk of phase separation. However, La₂O₃ provides a higher density compared to other high-refractive-index components (e.g., TiO₂, Nb₂O₅, or WO₃). Moreover, when added in large quantities, it may cause refractory materials (e.g., lanthanum disilicate (La₂Si₂O₇) and lanthanum zirconate (La₂ZrO₅), or solid solutions containing these minerals) to crystallize, which may increase the liquidus temperature of the glass and thus potentially reduce its glass-forming ability. For this reason, the La₂O₃ content in the glass of this disclosure should be limited. In embodiments, the amount of lanthanum oxide (La₂O₃) contained in the glass composition may be greater than or equal to 0.0 mol% to less than or equal to 35.0 mol%, and all ranges and subranges between these values. In some embodiments, the amount of La2O3 contained in the glass composition may be: greater than or equal to 0.0 mol%, greater than or equal to 5.0 mol%, greater than or equal to 15.0 mol%, greater than or equal to 17.5 mol%, greater than or equal to 20.0 mol%, greater than or equal to 21.0 mol%, greater than or equal to 23.5 mol%, greater than or equal to 25.0 mol%, or greater than or equal to 30.0 mol%. In some other embodiments, the amount of La2O3 contained in the glass composition may be: less than or equal to 35.0 mol%, less than or equal to 30.0 mol%, less than or equal to 27.5 mol%, less than or equal to 26.25 mol%, less than or equal to 25.5 mol%, less than or equal to 25.0 mol%, less than or equal to 20.0 mol%, or less than or equal to 5.0 mol%.In some further embodiments, the amount of La2O3 contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 30.0 mol%, greater than or equal to 15.0 mol% and less than or equal to 30.0 mol%, greater than or equal to 17.5 mol% and less than or equal to 27.5 mol%, greater than or equal to 20.0 mol% and less than or equal to 30.0 mol%, greater than or equal to 20.0 mol% and less than or equal to 27.5 mol%, greater than or equal to 21.0 mol% and less than or equal to 26.25 mol%, and greater than or equal to 23.51 mol% and less than or equal to 25.54 mol%. mol%, greater than or equal to 0.0 mol% and less than or equal to 35.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 20.0 mol% and less than or equal to 25.0 mol%, greater than or equal to 25.0 mol% and less than or equal to 25.5 mol%, greater than or equal to 25.5 mol% and less than or equal to 35.0 mol%, greater than or equal to 25.5 mol% and less than or equal to 26.25 mol%, greater than or equal to 26.25 mol% and less than or equal to 27.5 mol%.
[0067] In embodiments, the amount of yttrium oxide (Y₂O₃) contained in the glass composition can be greater than or equal to 0.0 mol% to less than or equal to 10.0 mol%, and all ranges and subranges between the above values. In some embodiments, the amount of Y₂O₃ contained in the glass composition can be: greater than or equal to 0.0 mol%, greater than or equal to 0.5 mol%, greater than or equal to 0.75 mol%, greater than or equal to 1.0 mol%, greater than or equal to 5.0 mol%, greater than or equal to 7.0 mol%, greater than or equal to 8.0 mol%, or greater than or equal to 9.0 mol%. In some other embodiments, the amount of Y₂O₃ contained in the glass composition can be: less than or equal to 10.0 mol%, less than or equal to 9.0 mol%, less than or equal to 8.0 mol%, less than or equal to 7.5 mol%, less than or equal to 7.0 mol%, less than or equal to 6.7 mol%, less than or equal to 6.25 mol%, less than or equal to 6.0 mol%, less than or equal to 5.5 mol%, less than or equal to 5.0 mol%, less than or equal to 4.6 mol%, or less than or equal to 3.0 mol%. In some further embodiments, the amount of Y₂O₃ contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 7.5 mol%, greater than or equal to 0.0 mol% and less than or equal to 6.7 mol%, greater than or equal to 0.0 mol% and less than or equal to 6.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 4.6 mol%, greater than or equal to 0.5 mol% and less than or equal to 6.25 mol%, and greater than or equal to 0.75 mol%. % and less than or equal to 5.5 mol%, greater than or equal to 0.89 mol% and less than or equal to 3.43 mol%, greater than or equal to 0.0 mol% and less than or equal to 3.0 mol%, greater than or equal to 3.0 mol% and less than or equal to 4.6 mol%, greater than or equal to 4.6 mol% and less than or equal to 10.0 mol%, greater than or equal to 4.6 mol% and less than or equal to 5.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 5.5 mol%, greater than or equal to 5.5 mol% and less than or equal to 10.0 mol%.
[0068] In embodiments, the amount of gadolinium oxide (Gd₂O₃) contained in the glass composition can be greater than or equal to 0.0 mol% to less than or equal to 5.0 mol%, and all ranges and subranges between the above values. In some other embodiments, the amount of Gd₂O₃ contained in the glass composition can be: less than or equal to 5.0 mol%, less than or equal to 2.5 mol%, less than or equal to 2.0 mol%, less than or equal to 1.5 mol%, less than or equal to 1.35 mol%, less than or equal to 1.2 mol%, or less than or equal to 0.42 mol%. In some further embodiments, the amount of Gd2O3 contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 2.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 1.5 mol%, greater than or equal to 0.0 mol% and less than or equal to 1.35 mol%, greater than or equal to 0.0 mol% and less than or equal to 1.2 mol%, greater than or equal to 0.29 mol% and less than or equal to 0.42 mol%, greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%, and greater than or equal to 0.0 mol% and less than or equal to 0.42 mol%.
[0069] In embodiments, the amount of ytterbium oxide (Yb₂O₃) contained in the glass composition can be greater than or equal to 0.0 mol% to less than or equal to 5.0 mol%, and all ranges and subranges between the above values. In some other embodiments, the amount of Yb₂O₃ contained in the glass composition can be: less than or equal to 5.0 mol%, less than or equal to 2.5 mol%, less than or equal to 1.0 mol%, less than or equal to 0.9 mol%, or less than or equal to 0.8 mol%. In some more embodiments, the amount of Yb₂O₃ contained in the glass composition can be: greater than or equal to 0.0 mol% and less than or equal to 1.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 0.9 mol%, greater than or equal to 0.0 mol% and less than or equal to 0.8 mol%, greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%.
[0070] Glass compositions may contain divalent metal oxides (ROs). Adding divalent metal oxides to glass, such as alkaline earth metal oxides (BeO, MgO, CaO, SrO, and BaO), zinc oxide (ZnO), cadmium oxide (CdO), lead oxide (PbO), and others, provides considerably higher refractive indices than most monovalent oxides. Some divalent metal oxides (e.g., CaO, SrO, and ZnO) also provide considerably lower densities, thus increasing the refractive index-density ratio and consequently improving the performance of optical glasses in certain applications. Furthermore, divalent metal oxides can help increase the solubility of high-refractive-index components (e.g., TiO2, Nb2O5, and WO3), which indirectly leads to a further increase in refractive index at comparable densities. Additionally, some divalent metal oxides (e.g., ZnO and MgO) provide considerably lower coefficients of thermal expansion, which can reduce thermal stresses formed in glass articles upon cooling and thus improve the quality of the glass articles. However, when added in large quantities, divalent metal oxides may cause refractory minerals to crystallize from the melt or undergo liquid-liquid phase separation, which may reduce the glass's glass-forming ability. Furthermore, some divalent metal oxides (e.g., PbO and CdO) may raise some ecological concerns. Therefore, the amount of divalent metal oxides in the glass compositions of this disclosure is limited.
[0071] In some embodiments, the amount of divalent metal oxide RO contained in the glass composition may be greater than or equal to 0.0 mol%, greater than or equal to 10.0 mol%, or greater than or equal to 20.0 mol%. In some other embodiments, the amount of divalent metal oxide RO contained in the glass composition may be less than or equal to 25.0 mol%, less than or equal to 20.0 mol%, or less than or equal to 10.0 mol%. In some more embodiments, the amount of divalent metal oxide RO contained in the glass composition may be greater than or equal to 0.0 mol% and less than or equal to 25.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 20.0 mol%, or greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 10.0 mol% and less than or equal to 25.0 mol%, or greater than or equal to 10.0 mol% and less than or equal to 20.0 mol%.
[0072] Glass compositions may contain calcium oxide (CaO). Among known monovalent and divalent metal oxides, calcium oxide provides the highest refractive index-density ratio for glasses. Furthermore, in some embodiments, CaO can help increase the solubility of Nb₂O₅ and TiO₂, which has an additional contribution to increasing the refractive index at relatively low densities. However, if the amount of CaO in the glass is too high, it may cause refractory materials (e.g., calcium titanate (CaTiO₃, CaTi₂O₅, etc.), calcium niobate (CaNb₂O₆), calcium metasilicate (CaSiO₃), and others) to crystallize, which may lower the viscosity at the liquidus temperature and thus increase the critical cooling rate, potentially causing the glass-forming melt to crystallize upon cooling. This is why the amount of CaO in the glass of this disclosure is limited, or the glass may be substantially CaO-free. In embodiments, the amount of calcium oxide (CaO) contained in the glass composition may be greater than or equal to 0.0 mol% to less than or equal to 20.0 mol%, and all ranges and subranges between these values. In some embodiments, the amount of CaO contained in the glass composition may be: greater than or equal to 0.0 mol%, greater than or equal to 2.0 mol%, greater than or equal to 5.0 mol%, greater than or equal to 10.0 mol%, greater than or equal to 14.0 mol%, greater than or equal to 16.0 mol%, or greater than or equal to 18.0 mol%. In some other embodiments, the amount of CaO contained in the glass composition may be: less than or equal to 20.0 mol%, less than or equal to 18.0 mol%, less than or equal to 16.0 mol%, less than or equal to 14.0 mol%, less than or equal to 10.0 mol%, less than or equal to 9.0 mol%, less than or equal to 8.0 mol%, less than or equal to 6.5 mol%, less than or equal to 6.0 mol%, or less than or equal to 5.0 mol%. In some further embodiments, the amount of CaO contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 9.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 8.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 6.5 mol%, greater than or equal to 1.99 mol% and less than or equal to 6.49 mol%, greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 6.0 mol%, greater than or equal to 6.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 6.5 mol% and less than or equal to 20.0 mol%, greater than or equal to 8.0 mol% and less than or equal to 9.0 mol%.
[0073] The glass composition may contain barium oxide (BaO). Barium oxide can increase the solubility of high refractive index enhancer components (e.g., TiO2 and Nb2O5), which can indirectly lead to a further increase in refractive index at relatively low densities. However, barium is a heavy element and its addition in large quantities may increase the glass density. Furthermore, at high concentrations, it may cause such minerals to crystallize as barium titanate (BaTiO3), barium niobate (BaNb2O6), and others. Therefore, the amount of BaO in the glass of this disclosure is limited, or the glass may be substantially free of BaO. In embodiments, the amount of barium oxide (BaO) contained in the glass composition may be greater than or equal to 0.0 mol% to less than or equal to 10.0 mol%, and all ranges and subranges between the above values. In some embodiments, the amount of BaO contained in the glass composition may be: greater than or equal to 0.0 mol%, greater than or equal to 2.0 mol%, greater than or equal to 5.0 mol%, greater than or equal to 7.0 mol%, or greater than or equal to 8.0 mol%, or greater than or equal to 9.0 mol%. In some other embodiments, the amount of BaO contained in the glass composition may be: less than or equal to 10.0 mol%, less than or equal to 9.0 mol%, less than or equal to 8.0 mol%, less than or equal to 7.5 mol%, less than or equal to 7.0 mol%, less than or equal to 6.5 mol%, less than or equal to 6.0 mol%, less than or equal to 5.5 mol%, less than or equal to 5.0 mol%, or less than or equal to 3.0 mol%. In some further embodiments, the amount of BaO contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 7.5 mol%, greater than or equal to 0.0 mol% and less than or equal to 6.5 mol%, greater than or equal to 0.0 mol% and less than or equal to 5.5 mol%, greater than or equal to 0.0 mol% and less than or equal to 3.0 mol%, greater than or equal to 1.5 mol% and less than or equal to 6.48 mol%, greater than or equal to 3.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 5.5 mol% and less than or equal to 10.0 mol%, greater than or equal to 5.5 mol% and less than or equal to 6.0 mol%, and greater than or equal to 6.0 mol% and less than or equal to 6.5 mol%.
[0074] The glass composition may contain zinc oxide (ZnO). Zinc oxide provides a good refractive index-density ratio and can sometimes increase the solubility of titanium oxide, which indirectly increases the refractive index of the glass. However, it has been found in some embodiments that, at high concentrations of ZnO, the glass-forming ability of the melt decreases and the melt may tend to crystallize during cooling. In embodiments, the amount of zinc oxide (ZnO) contained in the glass composition may be greater than or equal to 0.0 mol% to less than or equal to 10.0 mol%, and all ranges and subranges between the above values. In some embodiments, the amount of ZnO contained in the glass composition may be: greater than or equal to 0.0 mol%, greater than or equal to 0.3 mol%, greater than or equal to 5.0 mol%, greater than or equal to 7.0 mol%, greater than or equal to 8.0 mol%, or greater than or equal to 9.0 mol%. In some other embodiments, the amount of ZnO contained in the glass composition may be: less than or equal to 10.0 mol%, less than or equal to 9.0 mol%, less than or equal to 8.0 mol%, less than or equal to 7.0 mol%, less than or equal to 5.0 mol%, less than or equal to 4.0 mol%, less than or equal to 3.5 mol%, less than or equal to 3.0 mol%, less than or equal to 2.7 mol%, less than or equal to 2.5 mol%, less than or equal to 2.3 mol%, or less than or equal to 0.1 mol%. In some further embodiments, the amount of ZnO contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 4.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 3.5 mol%, greater than or equal to 0.0 mol% and less than or equal to 3.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 2.7 mol%, greater than or equal to 0.0 mol% and less than or equal to 2.5 mol%, greater than or equal to 0.0 mol% and less than or equal to 0.1 mol%, greater than or equal to 0.31 mol% and less than or equal to 2.32 mol%, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 0.1 mol% and less than or equal to 10.0 mol%, greater than or equal to 2.3 mol% and less than or equal to 2.5 mol%, greater than or equal to 2.5 mol% and less than or equal to 2.7 mol%, and greater than or equal to 2.7 mol% and less than or equal to 3.0 mol%.
[0075] The glass composition may contain strontium oxide (SrO). In some glasses, SrO, similar to CaO, can improve the solubility of the refractive index enhancer. However, at comparable refractive indices, SrO provides a slightly higher density than CaO. Therefore, the amount of SrO in the glasses of this disclosure is limited, or the glasses may be substantially free of SrO. In embodiments, the amount of strontium oxide (SrO) contained in the glass composition may be greater than or equal to 0.0 mol% to less than or equal to 5.0 mol%, and all ranges and subranges between the above values. In some other embodiments, the amount of SrO contained in the glass composition may be: less than or equal to 5.0 mol%, less than or equal to 2.5 mol%, less than or equal to 1.0 mol%, less than or equal to 0.9 mol%, less than or equal to 0.8 mol%, or less than or equal to 0.05 mol%. In some further embodiments, the amount of SrO contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 1.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 0.9 mol%, greater than or equal to 0.0 mol% and less than or equal to 0.8 mol%, greater than or equal to 0.03 mol% and less than or equal to 0.05 mol%, greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%, and greater than or equal to 0.0 mol% and less than or equal to 0.05 mol%.
[0076] Glass compositions may contain monovalent metal oxides (R₂O). Monovalent metal oxides (e.g., alkali metal oxides (Li₂O, Na₂O, K₂O, Rb₂O, and Cs₂O) or others (e.g., Ag₂O or Tl₂O)) can help to better accommodate refractive index enhancers (e.g., TiO₂, Nb₂O₅, or WO₃) in the glass structure, which leads to increased solubility of these enhancers in the glass and thus directly results in an increase in refractive index at acceptable low densities.
[0077] In some embodiments, the amount of monovalent metal oxide R2O contained in the glass composition may be greater than or equal to 0.0 mol%, greater than or equal to 10.0 mol%, or greater than or equal to 20.0 mol%. In some other embodiments, the amount of monovalent metal oxide R2O contained in the glass composition may be less than or equal to 25.0 mol%, less than or equal to 20.0 mol%, or less than or equal to 10.0 mol%. In some more embodiments, the amount of R2O contained in the glass composition may be greater than or equal to 0.0 mol% and less than or equal to 25.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 20.0 mol%, or greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 10.0 mol% and less than or equal to 25.0 mol%, or greater than or equal to 10.0 mol% and less than or equal to 20.0 mol%.
[0078] The glass composition may contain alumina (Al2O3). Alumina can increase the viscosity of the glass-forming melt at high temperatures, which can reduce the critical cooling rate and improve glass forming ability. However, the addition of Al2O3 may cause the crystallization of refractory minerals (e.g., aluminum titanate (Al2TiO5), aluminum niobate (AlNbO4), and others) in the melt upon cooling, or may reduce the solubility of ZrO2 in the liquid, resulting in an increase in the liquidus temperature. Therefore, the amount of Al2O3 in the glass of this disclosure is limited, or the glass may be substantially free of Al2O3. In embodiments, the amount of alumina (Al2O3) contained in the glass composition may be greater than or equal to 0.0 mol% to less than or equal to 10.0 mol%, and all ranges and subranges between the above values. In some embodiments, the amount of Al2O3 contained in the glass composition may be: greater than or equal to 0.0 mol%, greater than or equal to 5.0 mol%, greater than or equal to 7.0 mol%, greater than or equal to 8.0 mol%, or greater than or equal to 9.0 mol%. In some other embodiments, the amount of Al2O3 contained in the glass composition may be: less than or equal to 10.0 mol%, less than or equal to 9.0 mol%, less than or equal to 8.0 mol%, less than or equal to 7.0 mol%, or less than or equal to 5.0 mol%. In some more embodiments, the amount of Al2O3 contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 7.0 mol%, greater than or equal to 7.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 7.0 mol% and less than or equal to 8.0 mol%, greater than or equal to 8.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 8.0 mol% and less than or equal to 9.0 mol%.
[0079] The glass composition may contain molybdenum oxide (MoO3). Adding MoO3 to the glass composition may increase the refractive index at a low density, but this can lead to undesirable coloration. For this reason, the MoO3 content is limited. In embodiments, the amount of molybdenum oxide (MoO3) contained in the glass composition may be greater than or equal to 0.0 mol% to less than or equal to 10.0 mol%, and all ranges and subranges between the above values. In some embodiments, the amount of MoO3 contained in the glass composition may be: greater than or equal to 0.0 mol%, greater than or equal to 5.0 mol%, greater than or equal to 7.0 mol%, greater than or equal to 8.0 mol%, or greater than or equal to 9.0 mol%. In some other embodiments, the amount of MoO3 contained in the glass composition may be: less than or equal to 10.0 mol%, less than or equal to 9.0 mol%, less than or equal to 8.0 mol%, less than or equal to 7.0 mol%, or less than or equal to 5.0 mol%. In some further embodiments, the amount of MoO3 contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 7.0 mol%, greater than or equal to 7.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 7.0 mol% and less than or equal to 8.0 mol%, greater than or equal to 8.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 8.0 mol% and less than or equal to 9.0 mol%.
[0080] The glass composition may contain tellurium oxide (TeO2). In the cases described in this disclosure, tellurium oxide behaves substantially similarly to bismuth oxide; furthermore, TeO2 is very expensive. Therefore, the tellurium oxide content should be limited, or the glass composition may be TeO2-free. In embodiments, the amount of tellurium oxide (TeO2) contained in the glass composition may be greater than or equal to 0.0 mol% to less than or equal to 20.0 mol%, and all ranges and subranges between the above values. In some embodiments, the amount of TeO2 contained in the glass composition may be: greater than or equal to 0.0 mol%, greater than or equal to 5.0 mol%, greater than or equal to 10.0 mol%, greater than or equal to 14.0 mol%, greater than or equal to 16.0 mol%, or greater than or equal to 18.0 mol%. In some other embodiments, the amount of TeO2 contained in the glass composition may be: less than or equal to 20.0 mol%, less than or equal to 18.0 mol%, less than or equal to 16.0 mol%, less than or equal to 14.0 mol%, less than or equal to 10.0 mol%, less than or equal to 5.0 mol%, or less than or equal to 2.0 mol%. In some further embodiments, the amount of TeO2 contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 2.0 mol%, greater than or equal to 2.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 2.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 10.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 10.0 mol% and less than or equal to 14.0 mol%, greater than or equal to 14.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 14.0 mol% and less than or equal to 16.0 mol%.
[0081] The glass composition may contain vanadium oxide (V₂O₅). Of all oxides, vanadium oxide offers the highest refractive index-density ratio. However, vanadium oxide can cause an undesirable dark hue and may also raise environmental concerns. For these reasons, the vanadium oxide content in the glass of this disclosure is limited, or the glass composition may be V₂O₅-free. In embodiments, the amount of vanadium oxide (V₂O₅) contained in the glass composition may be greater than or equal to 0.0 mol% to less than or equal to 10.0 mol%, and all ranges and subranges between the above values. In some embodiments, the amount of V₂O₅ contained in the glass composition may be: greater than or equal to 0.0 mol%, greater than or equal to 5.0 mol%, greater than or equal to 7.0 mol%, greater than or equal to 8.0 mol%, or greater than or equal to 9.0 mol%. In some other embodiments, the amount of V2O5 contained in the glass composition may be: less than or equal to 10.0 mol%, less than or equal to 9.0 mol%, less than or equal to 8.0 mol%, less than or equal to 7.0 mol%, less than or equal to 5.0 mol%, less than or equal to 4.0 mol%, or less than or equal to 0.1 mol%. In some further embodiments, the amount of V2O5 contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 4.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 0.1 mol%, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 0.1 mol% and less than or equal to 10.0 mol%, greater than or equal to 0.1 mol% and less than or equal to 4.0 mol%, greater than or equal to 4.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 4.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 7.0 mol%.
[0082] The glass composition may contain gallium oxide (Ga2O3). Gallium oxide plays a similar role to Al2O3 (increasing viscosity), but has a lower effect on the liquidus temperature, which allows for an increase in liquidus viscosity and thus improves the glass forming ability. However, gallium oxide is expensive, and its addition disadvantageously increases batch costs. Therefore, the amount of Ga2O3 in the glass of this disclosure is limited, or the glass may be substantially free of Ga2O3. In embodiments, the amount of gallium oxide (Ga2O3) contained in the glass composition may be greater than or equal to 0.0 mol% to less than or equal to 10.0 mol%, and all ranges and subranges between the above values. In some embodiments, the amount of Ga2O3 contained in the glass composition may be greater than or equal to 0.0 mol%, or greater than or equal to 5.0 mol%. In some other embodiments, the amount of Ga2O3 contained in the glass composition may be less than or equal to 10.0 mol%, less than or equal to 8.0 mol%, less than or equal to 7.5 mol%, or less than or equal to 5.0 mol%. In some further embodiments, the amount of Ga2O3 contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 8.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 7.5 mol%, greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 10.0 mol%, and greater than or equal to 5.0 mol% and less than or equal to 7.5 mol%.
[0083] The glass composition may contain tantalum oxide (Ta₂O₅). Tantalum oxide increases the refractive index while maintaining an acceptable density without reducing blue light transmittance. However, when added to a glass composition (sometimes even in small amounts), Ta₂O₅ can cause the crystallization of refractory minerals. Therefore, the content of tantalum oxide should be limited, or the glass composition may be Ta₂O₅-free. In embodiments, the amount of tantalum oxide (Ta₂O₅) contained in the glass composition may be greater than or equal to 0.0 mol% to less than or equal to 5.0 mol%, and all ranges and subranges between the above values. In some other embodiments, the amount of Ta₂O₅ contained in the glass composition may be: less than or equal to 5.0 mol%, less than or equal to 2.5 mol%, less than or equal to 2.0 mol%, or less than or equal to 1.0 mol%. In some more embodiments, the amount of Ta₂O₅ contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 2.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 1.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%.
[0084] The glass composition may contain bismuth oxide (Bi₂O₃). Bi₂O₃ provides a very high refractive index, but results in an increased density. However, it may reduce the melt viscosity at high temperatures, which could cause the melt to crystallize upon cooling. Therefore, the bismuth oxide content should be limited, or the glass composition may be Bi₂O₃-free. In embodiments, the amount of bismuth oxide (Bi₂O₃) contained in the glass composition may be greater than or equal to 0.0 mol% to less than or equal to 20.0 mol%, and all ranges and subranges between the above values. In some embodiments, the amount of Bi₂O₃ contained in the glass composition may be: greater than or equal to 0.0 mol%, greater than or equal to 5.0 mol%, greater than or equal to 10.0 mol%, greater than or equal to 14.0 mol%, greater than or equal to 16.0 mol%, or greater than or equal to 18.0 mol%. In some other embodiments, the amount of Bi2O3 contained in the glass composition may be: less than or equal to 20.0 mol%, less than or equal to 18.0 mol%, less than or equal to 16.0 mol%, less than or equal to 14.0 mol%, less than or equal to 10.0 mol%, or less than or equal to 5.0 mol%. In some further embodiments, the amount of Bi2O3 contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 10.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 10.0 mol% and less than or equal to 14.0 mol%, greater than or equal to 14.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 14.0 mol% and less than or equal to 16.0 mol%, greater than or equal to 16.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 16.0 mol% and less than or equal to 18.0 mol%.
[0085] The glass composition may contain tungsten oxide (WO3). WO3 provides a high refractive index without significantly increasing density or causing undesirable coloration. Furthermore, it has been empirically found that adding WO3 to the glass composition lowers the liquidus temperature, allowing such glasses to melt at lower temperatures, which in turn increases their transmittance. Additionally, adding WO3 can lower the glass transition temperature Tg. gThis allows for the formation of these glasses at lower temperatures. At high concentrations of WO3, the liquidus temperature tends to increase, and the viscosity at the liquidus temperature decreases, making it difficult to avoid crystallization of the melt upon cooling. Therefore, the WO3 content should be limited, or the glass composition may be WO3-free. In embodiments, the amount of tungsten oxide (WO3) contained in the glass composition can be greater than or equal to 0.0 mol% to less than or equal to 5.0 mol%, and all ranges and subranges between these values. In some other embodiments, the amount of WO3 contained in the glass composition can be: less than or equal to 5.0 mol%, less than or equal to 2.5 mol%, less than or equal to 2.0 mol%, less than or equal to 1.8 mol%, less than or equal to 1.6 mol%, or less than or equal to 1.0 mol%. In some further embodiments, the amount of WO3 contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 2.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 1.8 mol%, greater than or equal to 0.0 mol% and less than or equal to 1.6 mol%, greater than or equal to 0.0 mol% and less than or equal to 1.0 mol%, and greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%.
[0086] The glass composition may contain zirconium oxide (ZrO2). Zirconia can increase the refractive index while maintaining an acceptablely low density. ZrO2 also increases the viscosity of the melt, which helps protect the melt from crystallization. ZrO2 does not introduce color into the glass in the visible and near-UV range, which helps maintain the glass's high transmittance. However, high concentrations of zirconium oxide can cause crystallization of refractory minerals (e.g., zirconium oxide (ZrO2), zircon (ZrSiO4), calcium zirconate (CaZrO3), and others), which may reduce the glass-forming ability of the melt. In embodiments, the amount of zirconium oxide (ZrO2) contained in the glass composition can be greater than or equal to 0.0 mol% to less than or equal to 11.0 mol%, and all ranges and subranges between these values. In some embodiments, the amount of ZrO2 contained in the glass composition may be: greater than or equal to 0.0 mol%, greater than or equal to 1.0 mol%, greater than or equal to 4.0 mol%, greater than or equal to 5.0 mol%, greater than or equal to 5.3 mol%, greater than or equal to 5.6 mol%, greater than or equal to 6.5 mol%, greater than or equal to 7.3 mol%, greater than or equal to 8.0 mol%, greater than or equal to 9.0 mol%, or greater than or equal to 10.0 mol%. In some other embodiments, the amount of ZrO2 contained in the glass composition may be: less than or equal to 11.0 mol%, less than or equal to 10.0 mol%, less than or equal to 9.0 mol%, less than or equal to 8.1 mol%, less than or equal to 8.0 mol%, less than or equal to 5.0 mol%, or less than or equal to 1.0 mol%. In some further embodiments, the amount of ZrO2 contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 4.0 mol% and less than or equal to 9.0 mol%, greater than or equal to 5.3 mol% and less than or equal to 8.1 mol%, greater than or equal to 5.6 mol% and less than or equal to 8.0 mol%, greater than or equal to 6.5 mol% and less than or equal to 8.0 mol%, greater than or equal to 7.34 mol% and less than or equal to 7.98 mol%, greater than or equal to 0.0 mol% and less than or equal to 11.0 mol%, greater than or equal to 1.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 8.0 mol%, greater than or equal to 8.0 mol% and less than or equal to 8.1 mol%, and greater than or equal to 9.0 mol% and less than or equal to 10.0 mol%.
[0087] The glass composition may contain hafnium oxide (HfO2). In the cases described in this disclosure, hafnium oxide behaves substantially similarly to zirconium oxide; furthermore, HfO2 is expensive. Therefore, the content of hafnium oxide should be limited, or the glass composition may be HfO2-free. In embodiments, the amount of hafnium oxide (HfO2) contained in the glass composition may be greater than or equal to 0.0 mol% to less than or equal to 11.0 mol%, and all ranges and subranges between the above values. In some embodiments, the amount of HfO2 contained in the glass composition may be: greater than or equal to 0.0 mol%, greater than or equal to 1.0 mol%, greater than or equal to 4.0 mol%, greater than or equal to 5.0 mol%, greater than or equal to 5.3 mol%, greater than or equal to 5.6 mol%, greater than or equal to 6.5 mol%, greater than or equal to 7.3 mol%, greater than or equal to 8.0 mol%, greater than or equal to 9.0 mol%, or greater than or equal to 10.0 mol%. In some other embodiments, the amount of HfO2 contained in the glass composition may be: less than or equal to 11.0 mol%, less than or equal to 10.0 mol%, less than or equal to 9.0 mol%, less than or equal to 8.1 mol%, less than or equal to 8.0 mol%, less than or equal to 5.0 mol%, or less than or equal to 1.0 mol%. In some further embodiments, the amount of HfO2 contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 4.0 mol% and less than or equal to 9.0 mol%, greater than or equal to 5.3 mol% and less than or equal to 8.1 mol%, greater than or equal to 5.6 mol% and less than or equal to 8.0 mol%, greater than or equal to 6.5 mol% and less than or equal to 8.0 mol%, greater than or equal to 7.34 mol% and less than or equal to 7.98 mol%, greater than or equal to 0.0 mol% and less than or equal to 11.0 mol%, greater than or equal to 1.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 8.0 mol%, greater than or equal to 8.0 mol% and less than or equal to 8.1 mol%, and greater than or equal to 9.0 mol% and less than or equal to 10.0 mol%.
[0088] Glass compositions may contain niobium oxide (Nb₂O₅). Niobium oxide can be used to increase the refractive index of the glass while maintaining a low density. However, niobium oxide introduces a yellow tint into the glass that cannot be bleached in the same way as titanium oxide, leading to a loss of transmittance (particularly in the blue and UV ranges). Niobium oxide may cause crystallization and / or phase separation in the melt. In some embodiments, the glass may be substantially free of Nb₂O₅. In embodiments, the amount of niobium oxide (Nb₂O₅) contained in the glass composition may be greater than or equal to 0.0 mol% to less than or equal to 10.5 mol%, and all ranges and subranges between these values. In some embodiments, the amount of Nb₂O₅ contained in the glass composition may be: greater than or equal to 0.0 mol%, greater than or equal to 1.0 mol%, greater than or equal to 2.5 mol%, greater than or equal to 4.0 mol%, greater than or equal to 4.5 mol%, greater than or equal to 5.0 mol%, greater than or equal to 5.1 mol%, greater than or equal to 6.09 mol%, greater than or equal to 7.5 mol%, greater than or equal to 8.5 mol%, greater than or equal to 9.5 mol%, or greater than or equal to 10.0 mol%. In some other embodiments, the amount of Nb₂O₅ contained in the glass composition may be: less than or equal to 10.5 mol%, less than or equal to 10.0 mol%, less than or equal to 9.5 mol%, less than or equal to 9.25 mol%, less than or equal to 8.6 mol%, less than or equal to 8.5 mol%, less than or equal to 7.5 mol%, less than or equal to 6.7 mol%, less than or equal to 5.0 mol%, or less than or equal to 1.0 mol%. In some further embodiments, the amount of Nb₂O₅ contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 10.5 mol%, greater than or equal to 0.0 mol% and less than or equal to 6.75 mol%, greater than or equal to 2.5 mol% and less than or equal to 10.0 mol%, greater than or equal to 4.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 4.5 mol% and less than or equal to 9.25 mol%, greater than or equal to 5.0 mol% and less than or equal to 6.7 mol%, greater than or equal to 5.1 mol%. 8.6 mol% and less than or equal to 8.6 mol%, 6.09 mol% and less than or equal to 6.77 mol%, 0.0 mol% and less than or equal to 1.0 mol%, 7.5 mol% and less than or equal to 10.5 mol%, 8.5 mol% and less than or equal to 8.5 mol%, 8.5 mol% and less than or equal to 10.5 mol%, 8.5 mol% and less than or equal to 8.6 mol%, and 8.6 mol% and less than or equal to 9.25 mol%.
[0089] The glass composition may contain titanium dioxide (TiO2). The levels of TiO2 and / or Nb2O5 typically used in glass to increase the refractive index tend to reduce transmittance in the near-UV region and shift the UV cutoff to higher wavelengths. Therefore, the amount of TiO2 is limited. In embodiments, the amount of titanium dioxide (TiO2) contained in the glass composition can be greater than or equal to 0.0 mol% to less than or equal to 40.0 mol%, and all ranges and subranges between these values. In some embodiments, the amount of TiO2 contained in the glass composition can be: greater than or equal to 0.0 mol%, greater than or equal to 1.0 mol%, greater than or equal to 5.0 mol%, greater than or equal to 20.0 mol%, greater than or equal to 20.25 mol%, greater than or equal to 22.0 mol%, greater than or equal to 25.0 mol%, greater than or equal to 30.0 mol%, or greater than or equal to 35.0 mol%. In some other embodiments, the amount of TiO2 contained in the glass composition may be: less than or equal to 40.0 mol%, less than or equal to 35.0 mol%, less than or equal to 30.0 mol%, less than or equal to 28.0 mol%, less than or equal to 27.5 mol%, less than or equal to 26.0 mol%, less than or equal to 25.5 mol%, less than or equal to 25.2 mol%, less than or equal to 25.0 mol%, less than or equal to 23.0 mol%, less than or equal to 20.0 mol%, or less than or equal to 5.0 mol%. In some further embodiments, the amount of TiO2 contained in the glass composition may be: greater than or equal to 0.0 mol% and less than or equal to 25.2 mol%, greater than or equal to 1.0 mol% and less than or equal to 40.0 mol%, greater than or equal to 20.0 mol% and less than or equal to 28.0 mol%, greater than or equal to 20.0 mol% and less than or equal to 27.5 mol%, greater than or equal to 20.25 mol% and less than or equal to 26.0 mol%, greater than or equal to 20.25 mol% and less than or equal to 25.5 mol%, greater than or equal to 20.47 mol% and less than or equal to 23.3 mol%, greater than or equal to 22.0 mol%. mol% and less than or equal to 25.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 40.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 5.0 mol%, greater than or equal to 5.0 mol% and less than or equal to 40.0 mol%, greater than or equal to 20.0 mol% and less than or equal to 23.0 mol%, greater than or equal to 23.0 mol% and less than or equal to 25.0 mol%, greater than or equal to 25.0 mol% and less than or equal to 40.0 mol%, greater than or equal to 25.0 mol% and less than or equal to 25.2 mol%, greater than or equal to 25.2 mol% and less than or equal to 25.5 mol%.
[0090] In some embodiments, the glass composition may have a sum of CaO + SrO + BaO + Y2O3 of greater than or equal to 0.0 mol% or greater than or equal to 0.3 mol%.
[0091] In some embodiments, the glass composition having a La₂O₃+TiO₂+B₂O₃+SiO₂+ZrO₂+Nb₂O₅ content of 97.0 mol%, 98.0 mol%, or 99.0 mol%. In some further embodiments, the sum of the La₂O₃+TiO₂+B₂O₃+SiO₂+ZrO₂+Nb₂O₅ content in the glass composition may be greater than or equal to 97.0 mol% and less than or equal to 100 mol%.
[0092] In some embodiments, the glass composition having the sum of La2O3+TiO2+B2O3+SiO2+ZrO2+Nb2O5+BaO+Y2O3+CaO+Ga2O3+Gd2O3+ZnO+WO3+CeO2+SrO+Na2O+Ta2O5+Al2O3 can be greater than or equal to 99.0 mol%, or greater than or equal to 99.5 mol%. In some more embodiments, the glass composition having the sum of La2O3+TiO2+B2O3+SiO2+ZrO2+Nb2O5+BaO+Y2O3+CaO+Ga2O3+Gd2O3+ZnO+WO3+CeO2+SrO+Na2O+Ta2O5+Al2O3 can be greater than or equal to 99.0 mol% and less than or equal to 100 mol%.
[0093] In some embodiments, the glass composition may have a sum of La2O3+Y2O3+Gd2O3+TiO2 that is greater than or equal to 0.0 mol%, or greater than or equal to 45.3 mol%.
[0094] In some embodiments, the sum of La2O3+Y2O3+Gd2O3+TiO2+B2O3+SiO2+ZrO2+Nb2O5 in the glass composition may be greater than or equal to 99.0 mol%, or greater than or equal to 99.5 mol%. In some more embodiments, the sum of La2O3+Y2O3+Gd2O3+TiO2+B2O3+SiO2+ZrO2+Nb2O5 in the glass composition may be greater than or equal to 99.0 mol% and less than or equal to 100 mol%.
[0095] In some embodiments, the glass composition having a sum of La₂O₃+Y₂O₃+Gd₂O₃+TiO₂+B₂O₃+SiO₂+ZrO₂+Nb₂O₅+CaO+BaO can be greater than or equal to 99.0 mol%, or greater than or equal to 99.5 mol%. In some more embodiments, the glass composition having a sum of La₂O₃+Y₂O₃+Gd₂O₃+TiO₂+B₂O₃+SiO₂+ZrO₂+Nb₂O₅+CaO+BaO can be greater than or equal to 99.0 mol% and less than or equal to 100 mol%.
[0096] In some embodiments, the sum of La2O3+Yb2O3+Y2O3+Gd2O3+TiO2 in the glass composition may be greater than or equal to 0.0 mol%, or greater than or equal to 45.3 mol%.
[0097] In some embodiments, the glass composition may have a total Nb₂O₅ + ZrO₂ content of 0.0 mol%, 11.0 mol%, or 12.1 mol%.
[0098] In some embodiments, the glass composition may have a total R₂O + RO content of 0.0 mol%, 10.0 mol%, or 20.0 mol%. In other embodiments, the glass composition may have a total R₂O + RO content of 25.0 mol%, 20.0 mol%, 10.0 mol%, 6.0 mol%, or 1.0 mol%. In some further embodiments, the glass composition may have a sum of R2O and RO of: greater than or equal to 0.0 mol% and less than or equal to 25.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 6.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 1.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, greater than or equal to 10.0 mol% and less than or equal to 25.0 mol%, or greater than or equal to 10.0 mol% and less than or equal to 20.0 mol%.
[0099] In some embodiments, the sum of SiO2 and B2O3 in the glass composition may be greater than or equal to 0.0 mol%, greater than or equal to 10.0 mol%, or greater than or equal to 20.0 mol%. In some other embodiments, the sum of SiO2 and B2O3 in the glass composition may be less than or equal to 34.0 mol% or less than or equal to 20.0 mol%. In many more embodiments, the sum of SiO2 and B2O3 in the glass composition may be greater than or equal to 0.0 mol% and less than or equal to 34.0 mol%, or greater than or equal to 0.0 mol% and less than or equal to 20.0 mol%, greater than or equal to 10.0 mol% and less than or equal to 34.0 mol%, or greater than or equal to 10.0 mol% and less than or equal to 20.0 mol%.
[0100] In some embodiments, the glass composition may have a sum of SiO2 + B2O3 + P2O5 of 0.0 mol% or greater than or equal to 10.0 mol%.
[0101] In some embodiments, the glass composition may have limitations regarding the B2O3-SiO2 difference. Experience has shown that when the B2O3 content in the glass of this disclosure significantly exceeds the SiO2 content, the chemical durability of the glass may deteriorate, and the melt forming the glass may sometimes tend to undergo liquid-liquid separation. For this reason, in some embodiments, the difference (B2O3-SiO2) is limited. In some other embodiments, the glass may have a B2O3-SiO2 difference of less than or equal to 7.0 mol%.
[0102] In some embodiments, the glass composition may have limitations on the SiO2 / (SiO2+B2O3) ratio. Experience has shown that the simultaneous presence of SiO2 and B2O3 in the glass composition can improve the glass-forming ability of the melt and protect it from liquid-liquid separation. Higher SiO2 / (SiO2+B2O3) ratios can help improve chemical durability, while lower ratios can improve the solubility of the high-refractive-index components. In some embodiments, the glass may have a SiO2 / (SiO2+B2O3) ratio, in mol% of: greater than or equal to 0.0, greater than or equal to 0.38, or greater than or equal to 0.5. In some other embodiments, the glass may have a SiO2 / (SiO2+B2O3) ratio, in mol% of: less than or equal to 0.75, less than or equal to 0.5, or less than or equal to 0.4. In some further embodiments, the ratio of SiO2 / (SiO2+B2O3) of the glass, in mole percent, can be: greater than or equal to 0.0 and less than or equal to 0.4, greater than or equal to 0.38 and less than or equal to 0.75, greater than or equal to 0.0 and less than or equal to 0.75, greater than or equal to 0.0 and less than or equal to 0.5, greater than or equal to 0.38 and less than or equal to 0.5, or greater than or equal to 0.38 and less than or equal to 0.4.
[0103] In some embodiments, the glass composition may have limitations regarding the TiO2-B2O3 difference. A high (TiO2-B2O3) difference indirectly indicates a favorable relationship between refractive index and density, all other things being equal. In some embodiments, the glass may have a TiO2-B2O3 difference greater than or equal to -6.0 mol%.
[0104] In some embodiments, the glass composition may be limited by the TiO2-La2O3 difference. Both TiO2 and La2O3 provide high refractive indices. However, La2O3 provides higher blue light transmittance than TiO2. Therefore, a low (including negative) TiO2-La2O3 difference indirectly indicates a potentially higher blue light transmittance for a given refractive index value. In some other embodiments, the glass may have a TiO2-La2O3 difference of less than or equal to 5.0 mol%.
[0105] In some embodiments, the glass composition may have limitations regarding the Y₂O₃-Gd₂O₃ difference. Yttrium oxide and gadolinium oxide can be used as substitutes for La₂O₃. When used, yttrium oxide provides a lower density than gadolinium oxide. Therefore, to reduce density, yttrium oxide is preferred over gadolinium oxide. In some embodiments, the glass may have a Y₂O₃-Gd₂O₃ difference greater than or equal to -2.0 mol%.
[0106] In some embodiments, the glass composition may be limited by the difference between SiO2 + B2O3 and TiO2. This difference indirectly characterizes the balance between the glass-forming ability (increased with the addition of SiO2 and B2O3) and the blue light transmittance (decreased with the addition of TiO2). Higher values of the difference between SiO2 + B2O3 and TiO2 can improve glass-forming ability while maintaining higher blue light transmittance. In some embodiments, the glass may have a difference between SiO2 + B2O3 and TiO2 greater than or equal to 7.05 mol%.
[0107] In some embodiments, the glass has a room temperature density d RT It can be greater than or equal to 4.00 g / cm³ 3 Up to 6.00 g / cm³ 3 And all ranges and subranges between the above values. In some embodiments, the glass has a room temperature density d. RT It can be: greater than or equal to 4.00 g / cm³ 3 ≥4.50 g / cm³ 3 ≥4.80 g / cm³ 3 ≥5.00 g / cm³ 3 ≥5.01 g / cm³ 3 ≥5.40 g / cm³ 3 ≥5.60 g / cm³ 3 or greater than or equal to 5.80 g / cm³ 3 In some other embodiments, the glass has a room temperature density d. RT It can be: less than or equal to 6.00 g / cm³ 3 Less than or equal to 5.80 g / cm³ 3 Less than or equal to 5.60 g / cm³ 3 Less than or equal to 5.50 g / cm³ 3 Less than or equal to 5.40 g / cm³ 3 Less than or equal to 5.30 g / cm³ 3 Less than or equal to 5.12 g / cm³ 3 Less than or equal to 5.00 g / cm³3 or less than or equal to 4.50 g / cm³ 3 In some further embodiments, the glass has a room temperature density d RT It can be: greater than or equal to 4.00 g / cm³ 3 And less than or equal to 6.00 g / cm³ 3 ≥4.50 g / cm³ 3 And less than or equal to 5.50 g / cm 3 ≥4.00 g / cm³ 3 And less than or equal to 4.50 g / cm³ 3 ≥4.50 g / cm³ 3 And less than or equal to 6.00 g / cm³ 3 ≥4.50 g / cm³ 3 And less than or equal to 5.00 g / cm³ 3 ≥5.00 g / cm³ 3 And less than or equal to 5.12 g / cm³ 3 ≥5.12 g / cm³ 3 And less than or equal to 6.00 g / cm³ 3 ≥5.12 g / cm³ 3 And less than or equal to 5.30 g / cm 3 ≥5.30 g / cm³ 3 And less than or equal to 5.40 g / cm³ 3 .
[0108] In some embodiments, the glass has a refractive index n at 587.56 nm. d It can be greater than or equal to 1.950 to less than or equal to 2.070, and all ranges and subranges between the above values. In some embodiments, the glass has a refractive index n at 587.56 nm. d It can be: greater than or equal to 1.950, greater than or equal to 2.000, greater than or equal to 2.010, greater than or equal to 2.030, or greater than or equal to 2.050. In some other embodiments, the glass has a refractive index n at 587.56 nm. d It can be less than or equal to 2.070, less than or equal to 2.050, less than or equal to 2.030, less than or equal to 2.010, or less than or equal to 2.000. In some further embodiments, the glass has a refractive index n at 587.56 nm. dIt can be: greater than or equal to 1.950 and less than or equal to 2.070, greater than or equal to 1.950 and less than or equal to 2.000, greater than or equal to 2.000 and less than or equal to 2.070, greater than or equal to 2.000 and less than or equal to 2.010, greater than or equal to 2.010 and less than or equal to 2.070, greater than or equal to 2.010 and less than or equal to 2.030, greater than or equal to 2.030 and less than or equal to 2.070, greater than or equal to 2.030 and less than or equal to 2.050.
[0109] In some embodiments, the glass composition may have a liquidus temperature T of less than or equal to 1260°C. liq .
[0110] In some embodiments, the glass may have a transmittance TX greater than or equal to 85 at a wavelength of 460 nm. 460 nm ,%.
[0111] In some implementations, the glass may have a value n greater than or equal to 0.000. d -(1.207+0.155*d RT ).
[0112] In some implementations, the glass may have a value n greater than or equal to 0.000. d -(1.217+0.155*d RT ).
[0113] In some implementations, the glass may have a value greater than or equal to 0.000 (n) d -1) / d RT -(0.196+0.0016*(TiO2-La2O3)).
[0114] In some implementations, the glass may have a value greater than or equal to 0.000 (n) d -1) / d RT -(0.199+0.0016*(TiO2-La2O3)).
[0115] In some implementations, the glass may have a value greater than or equal to 0.000 (n) d -1) / d RT -(0.199+0.0025*(TiO2-La2O3)).
[0116] In some implementations, the glass may have a value greater than or equal to 0.000 (n) d -1) / d RT-(0.204+0.0025*(TiO2-La2O3)).
[0117] Refractive index n d Density d RT and refraction (n d -1) / d RT Glass properties can be predicted from the glass composition. Linear regression analysis was performed on exemplary glasses of this disclosure in the Examples section below, as well as other glass compositions documented in the literature, to determine the predictable refractive index n. d The equations relating the compositional dependence of density and refractive power.
[0118] A training dataset of glass compositions that meet the criteria specified in Table 1 below and have measured values of the properties of interest are randomly selected from publicly available literature data in the SciGlass Information System database and from exemplary glasses of the embodiments presented herein (each property (n) d Approximately 100 glass compositions (including density and refractive power) were used. Linear regression analysis was employed on the dataset specified above to determine the equations, eliminating irrelevant variables and outliers. Table 2 below presents the resulting equations. Another subset of glass compositions meeting the same criteria was used as a validation set to evaluate the ability to interpolate within predetermined compositional limits, corresponding to the standard deviations specified in Table 2. An external dataset of existing glass compositions (also randomly selected from the SciGlass Information System database) was used to evaluate the ability to predict properties falling outside the specified compositional limits with reasonable accuracy. This process was iterated multiple times to determine the optimal variables for each property, corresponding to the regression equations specified in Table 2.
[0119] Data on the composition of comparative glass used in linear regression modeling (including training, validation, and external datasets) were obtained from the publicly available SciGlass information system database. Equations (I), (II), and (III) were derived from the linear regression analysis and used to predict the refractive index n of the glass. d Density d RT and refractive power (n d -1) / d RT :
[0120] P n=1.844+0.0054162*La2O3+0.0031113*TiO2-0.004212*B2O3-0.0035692*SiO2+0.0027887*ZrO2+0.0078026*Nb2O5-0.00012928*CaO+0.00076566*BaO+0.0043601*Y2O3+0.00067408*ZnO+0.0068029*Gd2O3-0.0025106*Na2O+0.0039937*WO3-0.0043208*Al2O3-0.0011666*Li2O+0.0051727*PbO+0.012958*Bi2O3-0.0018753*GeO2-0.0014084*TeO2+0.0086647*Er2O3+0.0097345*Yb2O3-0.0038734*K2O-0.00041776*SrO-0.0017294*MgO,(I)
[0121] P d (g / cm 3 )=4.276+0.058714*La2O3-0.0077783*TiO2-0.023741*B2O3-0.018272*SiO2+0.010913*ZrO2-0.0014478*CaO+0.023857*BaO+0.033560*Y2O3+0.010174*ZnO+0.082094*Gd2O3-0.008237*Na2O+0.035497*WO3-0.031171*Al2O3-0.0080004*Li2O+0.051830*PbO+0.10437*Bi2O3-0.012816*GeO2-0.0065609*TeO2+0.10060*Er2O3+0.10637*Yb2O3-0.017097*K2O+0.009821*SrO-0.0037906*MgO,(II)
[0122] P ref (cm 3 / g)=0.201656+0.00018225*B2O3-0.0010873*BaO-0.0024853*Bi2O3-0.0030326*Er2O3-0.0018856*Gd2O3-0.0017563*La2O3-0.0002505*Na2O+0.0017526*N b2O5-0.0025472*Nd2O3-0.0016439*PbO+0.000050096*SiO2+0.0011794*TiO2- 0.00072112*WO3-0.00079167*Y2O3-0.0031015*Yb2O3-0.00034209*ZnO, (III)
[0123] In equations (I), (II), and (III) and in Tables 1 and 2, the refractive index parameter P n The refractive index n at 587.56 nm d The parameters used for prediction are calculated from the composition of the glass composition expressed in mole percent; density parameter P d The unit of expression is g / cm 3 room temperature density d RT The parameters used for prediction are calculated from the composition of the glass composition expressed in mol%; and the refractive power parameter Pref is a parameter used to predict the refractive index-density ratio (“refractive power”) (in cm). 3 / g), calculated from the components of the glass composition expressed in mole % (%).
[0124] In equations (I), (II), and (III), each component of the glass composition is listed in its chemical formula form, where the chemical formula refers to the concentration of the component (in mol%). For example, for the purposes of equations (I), (II), and (III), La2O5 refers to the concentration of La2O5 in the glass composition (expressed in mol%). It is to be understood that not all components listed in equations (I), (II), and (III) are necessarily present in a particular glass composition, and equations (I), (II), and (III) are equally applicable to glass compositions containing fewer than all the components listed in the equations. It is also to be understood that equations (I), (II), and (III) also apply to glass compositions within the scope of this disclosure and the claims containing components other than those listed in the equations. If a component listed in equations (I), (II), and (III) is absent in a particular glass composition, the concentration of that component in the glass composition is 0 mol% and the contribution of that component to the value calculated from the equations is zero.
[0125] Table 1: Composition space used for modeling
[0126]
[0127]
[0128] Table 2: Property Prediction Model
[0129]
[0130] Figure 1 The parameters P are those of some literature glasses (“comparative example glasses”) and some exemplary glasses (“example glasses”) calculated by equation (I). n The measured refractive index n d A graph showing the functional relationship. For example... Figure 1 The data shows that for most types of glass, parameter P... n The composition dependence has a measured n of ±0.017 units. d The error is within the range that corresponds to the standard deviation listed in Table 2.
[0131] Figure 2 The parameter P is calculated by equation (II) for some literature glass (“comparative example glass”) and some exemplary glass (“example glass”). d With the measured density d RT A graph showing the functional relationship. For example... Figure 2 The data shows that for most types of glass, parameter P... d The composition dependence has ±0.076 units of measured d RT The error is within the range that corresponds to the standard deviation listed in Table 2.
[0132] Figure 3 The parameters P are those obtained by equation (III) from some literature glasses (“comparative example glasses”) and some exemplary glasses (“example glasses”). ref With the measured refractive power (n) d -1) / d RT A graph showing the functional relationship. For example... Figure 3 The data shows that for most types of glass, parameter P... ref The composition dependence has a measurement of ±0.0031 units (n) d -1) / d RT The error is within the range that corresponds to the standard deviation listed in Table 2.
[0133] Table 3 identifies the combinations of components and their respective amounts in some embodiments according to this disclosure. The exemplary glass A in Table 3 may contain additional components according to any aspect of this disclosure described herein.
[0134] Table 3: Exemplary Glass A
[0135]
[0136]
[0137] The exemplary glass A according to the embodiments of this disclosure can satisfy the following conditions:
[0138] Y₂O₃-Gd₂O₃ [mol%] ≥ -2.0,
[0139] In the formula, the chemical formula refers to the amount of the component in the glass, expressed in moles.
[0140] According to some embodiments of this disclosure, exemplary glass A may also have a room temperature density d of 4 to 6. RT [g / cm 3 ].
[0141] According to some embodiments of this disclosure, exemplary glass A may also satisfy the following equation:
[0142] n d -(1.207+0.155*d RT )>0.000,
[0143] In the formula, n d It is the refractive index at 587.56 nm, and d RT It is the density at room temperature.
[0144] According to some embodiments of this disclosure, exemplary glass A may also satisfy the following equation:
[0145] n d -(1.217+0.155*d RT )>0.000,
[0146] In the formula, n d It is the refractive index at 587.56 nm, and d RT It is the density at room temperature.
[0147] Table 4 identifies the combinations of components and their respective amounts according to some embodiments of this disclosure. The exemplary glass B in Table 4 may contain additional components according to any aspect of this disclosure described herein.
[0148] Table 4: Exemplary Glass B
[0149]
[0150]
[0151] The exemplary glass B according to the embodiments of this disclosure can satisfy the following conditions:
[0152] SiO2+B2O3-TiO2 [mol%] ≥ 7.05
[0153] In the formula, the chemical formula refers to the amount of the component in the glass, expressed in moles.
[0154] According to some embodiments of this disclosure, exemplary glass B may also satisfy the following conditions:
[0155] B2O3-SiO2 [mol%] ≤ 7.0,
[0156] In the formula, the chemical formula refers to the amount of the component in the glass, expressed in moles.
[0157] According to some embodiments of this disclosure, exemplary glass B may also satisfy the following equation:
[0158] (n d -1) / d RT -(0.196+0.0016*(TiO2-La2O3))>0.000,
[0159] In the formula, (n d -1) / d RT It is the ratio of refractive index to density ("refractive power").
[0160] According to some embodiments of this disclosure, exemplary glass B may also satisfy the following equation:
[0161] (n d -1) / d RT -(0.199+0.0016*(TiO2-La2O3))>0.000,
[0162] In the formula, (n d -1) / d RT It is the ratio of refractive index to density ("refractive power").
[0163] Table 5 identifies the combinations of components and their respective amounts according to some embodiments of this disclosure. The exemplary glass C in Table 5 may contain additional components according to any aspect of this disclosure described herein.
[0164] Table 5: Exemplary Glass C
[0165]
[0166]
[0167] The exemplary glass C according to the embodiments of this disclosure can satisfy the following conditions:
[0168] TiO2-B2O3 [mol%] ≥ -6.0,
[0169] In the formula, the chemical formula refers to the amount of the component in the glass, expressed in moles.
[0170] According to some embodiments of this disclosure, the exemplary glass C may also satisfy the following conditions:
[0171] TiO2-La2O3 [mol%] ≤ 5.0,
[0172] In the formula, the chemical formula refers to the amount of the component in the glass, expressed in moles.
[0173] According to some embodiments of this disclosure, the exemplary glass C may also satisfy the following equation:
[0174] (n d -1) / d RT -(0.199+0.0025*(TiO2-La2O3))>0.000,
[0175] In the formula, (n d -1) / d RT It is the ratio of refractive index to density ("refractive power").
[0176] According to some embodiments of this disclosure, the exemplary glass C may also satisfy the following equation:
[0177] (n d -1) / d RT -(0.204+0.0025*(TiO2-La2O3))>0.000,
[0178] In the formula, (n d -1) / d RT It is the ratio of refractive index to density ("refractive power").
[0179] Example
[0180] The following examples illustrate the various features and advantages provided by this disclosure, and they do not in any way constitute a limitation of the invention or the appended claims.
[0181] To prepare glass samples of some exemplary glasses of this disclosure, approximately 15 grams of each sample (with a target component content greater than 99.99% by weight in the batch composition) were melted from the batch raw materials at a temperature of approximately 1300°C in a platinum or platinum-rhodium crucible (Pt:Rh = 80:20) for 1 hour. Two controlled cooling conditions were applied. In the first condition (referred to as the “15-minute test” or “15-minute devitrification test”), the cooling conditions were controlled such that the sample was cooled from 1100°C to 500°C in furnace air over approximately 15 minutes. In the second condition (referred to as the “2.5-minute test” or “2.5-minute devitrification test”), the cooling conditions were controlled such that the sample was cooled from 1100°C to 500°C in furnace air over approximately 2.5 minutes. Temperature readings were obtained either by direct reading of the furnace temperature or by reading from an IR camera with a calibrated scale. The first condition (15-minute test) approximately corresponds to a cooling rate of up to 300°C / min at a temperature of 1000°C, and the second test approximately corresponds to a cooling rate of up to 600°C / min at a temperature of 1000°C (1000°C approximately corresponds to the temperature at which the expected cooling rate is close to its maximum). The cooling rate decreases significantly as the temperature decreases. Figure 4 The diagram shows typical configurations for the first and second cooling methods. For these samples, observations referred to as the "15-minute devitrification test" and the "2.5-minute devitrification test" are specified in Table 6 below; an observation result "1" indicates that the glass composition passed the devitrification test, wherein the composition is considered to have passed the devitrification test if the melt of the composition forms glass without crystals visible under an optical microscope at 100x to 500x magnification. An observation result "0" indicates that the glass composition did not pass the devitrification test.
[0182] Unless otherwise stated, for the preparation of other glass samples of the exemplary glass of this disclosure, a 1 kg component batch is prepared in a pure platinum crucible. The crucible is placed in a furnace set at 1250°C, and then the furnace temperature is increased to 1300°C and held at 1300°C for 2 hours. The furnace temperature is then reduced to 1250°C, and the glass is allowed to cool naturally at this temperature to equilibrium for 1 hour, after which it is poured onto a steel stage and annealed at Tg for 1 hour.
[0183] Unless otherwise stated, in order to prepare some more samples of the exemplary glass of this disclosure, a 1 kg batch of components is prepared in a pure platinum crucible. The crucible is placed in a furnace at a set temperature of 1300°C to 1400°C for 3 hours, then poured onto a steel table and annealed at Tg for one hour.
[0184] Some sample melts were also melted in a one-liter platinum crucible heated by the Joule effect. Approximately 4800g of raw material was used in this process. The crucible was filled over 1.5 hours at a temperature of 1250–1300°C. The sample was then heated to 1300–1375°C and held for one hour. During this step, the glass was continuously stirred at 60 rpm. The sample was then cooled to 1250–1310°C to equilibrate for 30 minutes, and the stirring speed was reduced to 20 rpm. The transfer tube was heated to a maximum temperature of 1250–1310°C, and the glass was poured onto a cooled graphite stage. The glass was formed into rods approximately 25 mm thick, 50 mm wide, and 90 cm long. The prepared rods were examined under an optical microscope to check for crystallinity, and all were found to be free of crystals. The glass quality observed under the optical microscope was good; the rods were free of striae and bubbles. The glass was placed in a toughening furnace oven at Tg for 1 hour for rough annealing. Then, the bar was placed in a static furnace at Tg for annealing for 1 hour, and then the temperature was decreased at 1°C / min.
[0185] Some samples were bleached after melting to improve transmittance. The bleaching process was carried out at 500℃, with the crystallization initiation temperature Tc being the optimal temperature for crystallization. x The bleaching process is carried out at temperatures between 500°C and 500°C. When the temperature is below approximately 500°C, the bleaching process may take too long due to its slow rate. When the bleaching temperature exceeds T... x Glass can crystallize during heat treatment. Higher bleaching temperatures result in faster bleaching, but also lower transmittance values. Therefore, the bleaching temperature and time must be selected to achieve acceptable transmittance within a reasonable timeframe (e.g., less than or equal to 24 hours, or less than or equal to 48 hours, or less than or equal to 96 hours, or similar).
[0186] Some exemplary glass samples were exposed to Nano Strip 2X cleaning solution. The dried samples were immersed in 600 mL of Nano Strip 2X solution (Capitol Scientific, 85% H₂SO₄ and <1% H₂O₂) at 70°C for 50 minutes with stirring at 400 rpm. The surface area to volume ratio used for this test was 0.08 cm⁻². -1 After 50 minutes, the sample was quenched in deionized water and washed with 18 MΩ water, then dried under high-purity nitrogen and placed in a desiccator overnight. Weight loss was normalized relative to surface area (mg / cm²). 2 ), and calculate the percentage of weight loss (weight %).
[0187] No chemical analysis was performed on the test samples because similar samples prepared in independently melted batches were chemically analyzed by XRF (X-ray fluorescence, for all oxides except B2O3 and Li2O), ICP-OES (inductively coupled plasma optical emission spectroscopy, for B2O3), and FES (flame emission spectroscopy, for Li2O). These analyses yielded deviations of major components (e.g., Nb2O5) relative to the feed composition within ±2.0 wt%, which corresponds to less than approximately 1 mol%.
[0188] In Tables 6 and 7, the abbreviation "n" with a subscript refers to the refractive index at the corresponding wavelength (in nm); for example, n 632.8 nm This refers to the refractive index at a wavelength of 632.8 nm. T x This refers to the crystallization initiation temperature. TX 460 nm This refers to the total transmittance at a wavelength of 460 nm for a 10 mm thick glass sample after bleaching. Total transmittance is the transmittance measured using a Cary 5000 spectrometer without correction for Fresnel loss.
[0189] Table 6: Exemplary Glass Compositions
[0190]
[0191]
[0192]
[0193] Table 6 (continued)
[0194]
[0195]
[0196]
[0197] Table 6 (continued)
[0198]
[0199]
[0200]
[0201] Table 6 (continued)
[0202]
[0203]
[0204]
[0205] Table 6 (continued)
[0206]
[0207]
[0208]
[0209] Table 6 (continued)
[0210]
[0211]
[0212]
[0213] Table 6 (continued)
[0214]
[0215]
[0216] Table 6 (continued)
[0217]
[0218]
[0219]
[0220] Table 6 (continued)
[0221]
[0222]
[0223]
[0224] Table 7 below lists the glass composition and properties of comparative glass C1-C32.
[0225] Table 7: Composition and properties of comparative glass
[0226]
[0227]
[0228] Table 7 (continued)
[0229]
[0230]
[0231]
[0232] Table 7 (continued)
[0233]
[0234]
[0235] Table 7 (continued)
[0236]
[0237]
[0238]
[0239] The reference keys for each comparative glass listed in Table 7 are as follows: [1] SP20-266PZ; [2] SP21-055PZ; [3] US4584279A; [4] US8661853B2; [5] US8728963B2; [6] WO2012099168A1; [7] CN111320384; [8] TW202012333; [9] US4439531A;
[10] US9487432B2;
[11] WO2020045417A1.
[0240] Figure 5 The density parameter P of some exemplary glasses and some comparative glasses is shown. d With refractive index parameter P n The relationship diagram is shown. Exemplary glasses (solid circles) are Examples 2, 4, 6, 9, 11, 16 to 18, 20, 22, 25 to 47, 49, 50 and 53 to 55 from Table 6. Comparative example glasses (hollow circles) are Examples C1 to C6 from Table 7. The density parameter P for predicting room temperature density is determined according to Equation (II). d The refractive index parameter P for predicting the refractive index at 587.56 nm is determined based on equation (I). n . Figure 5 All exemplary and comparative glass examples shown have the characteristics specified in Table 8. In Table 8, the statement "no limitation" means that it is not considered a limitation when selecting the composition.
[0241] Table 8: Figure 5 Limitations of the glass composition shown
[0242] <![CDATA[B2O3]]> mole% 0.5 29 <![CDATA[TiO2]]> mole% 0 25.2 <![CDATA[Bi2O3]]> mole% 0 20 <![CDATA[TeO2]]> mole% 0 20 <![CDATA[P2O5]]> mole% 0 15 <![CDATA[Nb2O5]]> mole% 0 10.5 <![CDATA[Al2O3]]> mole% 0 10 <![CDATA[MoO3]]> mole% 0 5 <![CDATA[V2O5]]> mole% 0 4 <![CDATA[GeO2]]> mole% 0 2.5 ZnO mole% 0 2.5 <![CDATA[Ta2O5]]> mole% 0 1 <![CDATA[R m THE n ]]> mole% 95 No restrictions <![CDATA[RE m THE n ]]> mole% 0 29 <![CDATA[SiO2+B2O3+P2O5]]> mole% 10 No restrictions <![CDATA[SiO2+B2O3]]> mole% No restrictions 34 <![CDATA[CaO+SrO+BaO+Y2O3]]> mole% 0.3 No restrictions <![CDATA[R2O+RO]]> mole% 0 25 <![CDATA[Y2O3-Gd2O3]]> mole% -2 No restrictions <![CDATA[P d ]]> <![CDATA[g / cm 3 ]]> No restrictions 6
[0243] The comparative glass examples listed above were selected from known glasses that have the characteristics specified in Table 8, and have a comparable density parameter P. d The highest refractive index parameter P is obtained in the numerical case. n .
[0244] Figure 5 The line shown corresponding to the equation y = 1.207 + 0.155*x provides a visual representation of the differences between the comparative example glass with the properties specified in Table 8 and the exemplary glasses 2, 4, 6, 9, 11, 16 to 18, 20, 22, 25 to 47, 49, 50 and 53 to 55. Figure 5 It can be seen that, Figure 5 The exemplary glass (solid circle) mentioned herein falls above the line y = 1.207 + 0.155*x, and there is no comparative example glass (hollow circle) falling above the line y = 1.207 + 0.155*x, where y corresponds to the refractive index parameter P. n And x corresponds to the density parameter P. d In other words, Figure 5 Some of the exemplary glasses presented satisfy the following equation (IV)(a), and there are no comparative glass examples satisfying the following equation (IV)(a):
[0245] P n -(1.207+0.155*P d >0.00 (IV)(a)
[0246] from Figure 5 It can also be seen that, Figure 5 Some of the exemplary glass examples presented fall above the line y = 1.217 + 0.155*x, and there is no comparative example glass falling above the line y = 1.217 + 0.155*x, where y corresponds to the refractive index parameter P. n And x corresponds to the density parameter P. d In other words, Figure 5 Some of the exemplary glasses presented satisfy the following equation (IV)(b), and no comparative glass satisfies the following equation (IV)(b):
[0247] P n -(1.217+0.155*P d >0.00 (IV)(b)
[0248] In terms of prediction, Figure 5 The exemplary embodiments presented are for d RT and n d In terms of combination, it is superior to the best known comparative glass with the characteristics specified in Table 8.
[0249] Figure 6Showing some exemplary glass and some comparative glass, d RT With n d The relationship diagram is shown. Exemplary glass (solid circles) are Examples 2, 16 to 18, and 25 to 33 from Table 6. Comparative glass (hollow circles) are Examples C1, C5, and C6 from Table 7. Figure 6 All exemplary and comparative glass examples shown have the characteristics specified in Table 9. In Table 9, the statement "no limitation" means that it is not considered a limitation when selecting the composition.
[0250] Table 9: Figure 6 Limitations of the glass composition shown
[0251]
[0252]
[0253] The comparative glass examples listed above were selected from known glasses that have the characteristics specified in Table 9, and have a comparable d RT In numerical cases, n has the highest measured value. d Numerical value.
[0254] Figure 6 The line shown, corresponding to the equation y = 1.207 + 0.155*x, provides a visual representation of the differences between the comparative example glass with the characteristics specified in Table 9 and exemplary glasses 2, 16 to 18, and 25 to 33. Figure 6 It can be seen that, Figure 6 The exemplary glass (solid circle) mentioned in the text falls above the line y = 1.207 + 0.155*x, and there is no comparative example glass (hollow circle) falling above the line y = 1.207 + 0.155*x, where y corresponds to n. d And x corresponds to d RT In other words, Figure 6 Some of the exemplary glasses presented satisfy the following equation (V)(a), and there is no comparative glass that satisfies the following equation (V)(a):
[0255] n d -(1.207+0.155*d RT )>0.00(V)(a)
[0256] from Figure 6 It can also be seen that, Figure 6 Some of the exemplary glass examples presented above the line y = 1.217 + 0.155*x, and there is no comparative example glass above the line y = 1.217 + 0.155*x, where y corresponds to n. d And x corresponds to d RTIn other words, Figure 6 Some of the exemplary glasses presented satisfy the following equation (V)(b), and there are no comparative glass examples satisfying the following equation (V)(b):
[0257] n d -(1.217+0.155*d RT >0.00(V)(b)
[0258] According to measurements, Figure 6 The exemplary embodiments presented are for d RT and n d In terms of combination, it is superior to the best known comparative glass with the characteristics specified in Table 9.
[0259] The following table 10 presents Figure 5 and 6 Tables 8 and 9, which illustrate comparative example glasses C1 to C6, and the numerical values of all properties specified in equations (IV)(a), (IV)(b), (V)(a), and (V)(b) are provided. Table 7 presents the complete composition of the comparative example glasses. Table 6 presents the complete composition of exemplary glasses derived from this disclosure and the properties mentioned above.
[0260] Table 10: Comparative Examples of Glass Properties with Characteristics Specified in Tables 8 and 9
[0261]
[0262]
[0263] based on Figure 5 and 6 Both predicted and measured property data confirm that some exemplary glasses have better d properties compared to the best comparative glass with the corresponding properties specified in Tables 8 and 9. RT With n d The combination of .
[0264] The two main high-refractive-index components of the glass disclosed herein are titanium oxide (TiO2) and lanthanum oxide (La2O3). TiO2 provides a high refractive index with a lower density, but may result in some loss of blue light transmittance. La2O3 provides a higher blue light refractive index, but may increase density. Some glasses of this disclosure possess all three properties (refractive index n...). d density d RT The favorable combination of (and transmittance) results in a higher "refractive power" (n) for a given difference (TiO2-La2O3). d -1) / d RTNumerical values. In embodiments of this disclosure, other components (e.g., B2O3, SiO2, Nb2O5, CaO, BaO, Y2O3, and / or others) may be added to the glass composition. However, if these components are added at high concentrations, the refractive index decreases or the liquidus temperature increases, which may impair the glass-forming ability of the glass composition or may promote liquid-liquid phase separation, potentially leading to a loss of transmittance and / or crystallization of the melt forming the glass upon cooling. Therefore, the content of these components in the glass compositions of this disclosure is limited.
[0265] Figure 7 The difference in TiO2-La2O3 and the refractive power parameter P are shown for some exemplary glasses and some comparative glasses. ref The relationship diagram is shown. Exemplary glasses (solid circles) are Examples 1, 4 to 6, 14, 30, 35, 36 and 56 to 58 from Table 6. Comparative example glasses (hollow circles) are Examples C7 to C16 from Table 7. The refractive power parameter P, which predicts the refractive index-density ratio (“refractive power”), is determined according to Equation (III). ref . Figure 7 All exemplary and comparative glass examples shown have the characteristics specified in Table 11. In Table 11, the term "no limitation" means that it is not considered a limitation when selecting the composition.
[0266] Table 11: Figure 7 and 8 Limitations of the glass composition shown
[0267] <![CDATA[TiO2]]> mole% 1 40 <![CDATA[B2O3]]> mole% 1 40 <![CDATA[SiO2]]> mole% 0 35 <![CDATA[La2O3]]> mole% 0 30 <![CDATA[ZrO2]]> mole% 0 10 <![CDATA[GeO2]]> mole% 0 10 <![CDATA[Al2O3]]> mole% 0 10 <![CDATA[Nb2O5]]> mole% 0 6.75 <![CDATA[Y2O3]]> mole% 0 6.7 RO mole% 0 25 <![CDATA[R2O]]> mole% 0 25 <![CDATA[La2O3+Y2O3+Gd2O3+TiO2]]> mole% 45.3 No restrictions <![CDATA[Nb2O5+ZrO2]]> mole% 12.1 No restrictions <![CDATA[SiO2+B2O3-TiO2]]> mole% 7.05 No restrictions <![CDATA[B2O3-SiO2]]> mole% No restrictions 7
[0268] The comparative glass examples listed above were selected from known glasses that, among those exhibiting the characteristics specified in Table 11, possessed the highest refractive power parameter P while having a comparable TiO2–La2O3 difference. ref .
[0269] Figure 7 The line shown, corresponding to the equation y = 0.196 + 0.0016*x, provides a visual representation of the differences between the comparative example glass with the characteristics specified in Table 11 and exemplary glasses 1, 4 to 6, 14, 30, 35, 36, and 56 to 58. Figure 7 It can be seen that, Figure 7 The exemplary glass (solid circle) mentioned herein falls above the line y = 0.196 + 0.0016*x, and there is no comparative example glass (hollow circle) falling above the line y = 0.196 + 0.0016*x, where y corresponds to the refractive power parameter P. ref And x corresponds to the difference between TiO2 and La2O3. In other words, Figure 7Some of the exemplary glasses presented satisfy the following equation (VI)(a), and there are no comparative example glasses that satisfy the following equation (VI)(a):
[0270] P ref -(0.196+0.0016*(TiO2-La2O3))>0.0 (VI)(a)
[0271] from Figure 7 It can also be seen that, Figure 7 Some of the exemplary glass examples presented fall above the line y = 0.199 + 0.0016*x, and there is no comparative example glass falling above the line y = 0.199 + 0.0016*x, where y corresponds to the refractive power parameter P. ref And x corresponds to the difference between TiO2 and La2O3. In other words, Figure 7 Some of the exemplary glasses presented satisfy the following equation (VI)(b), and there are no comparative example glasses that satisfy the following equation (VI)(b):
[0272] P ref -(0.199+0.0016*(TiO2-La2O3))>0.0(VI)(b)
[0273] In terms of prediction, Figure 7 The exemplary embodiments presented are for TiO2–La2O3 and (n d -1) / d RT In terms of combination, it is superior to the best known comparative glass with the characteristics specified in Table 11.
[0274] Figure 8 Showing the TiO2–La2O3 difference and refractive index-density ratio (“refractive power”) of some exemplary glasses and some comparative glasses (n) d -1) / d RT The relationship diagram is shown. Exemplary glass (solid circles) are Examples 1 and 30 from Table 6. Comparative glass (hollow circles) are Examples C8, C9, and C11 to C17 from Table 7. Figure 8 All exemplary and comparative glass examples shown have the characteristics specified in Table 11. In Table 11, the term "no limitation" means that it is not considered a limitation when selecting the composition.
[0275] The comparative glass examples listed above were selected from known glasses having the specified characteristics mentioned in Table 11, and possessing the highest measured refractive index to density ratio (“refractive power”) with a comparable TiO2–La2O3 difference. d -1) / d RT .
[0276] Figure 8 The line shown, corresponding to the equation y = 0.196 + 0.0016*x, provides a visual representation of the differences between the comparative example glass with the characteristics specified in Table 11 and exemplary glasses 1 and 30. From Figure 8 It can be seen that, Figure 8 The exemplary glass (solid circle) mentioned in the text falls above the line y = 0.196 + 0.0016 * x, and there is no comparative example glass (hollow circle) falling above the line y = 0.196 + 0.0016 * x, where y corresponds to (n d -1) / d RT And x corresponds to the difference between TiO2 and La2O3. In other words, Figure 8 Some of the exemplary glasses presented satisfy the following equation (VII)(a), and there is no comparative glass that satisfies the following equation (VII)(a):
[0277] (n d -1) / d RT -(0.196+0.0016*(TiO2-La2O3))>0.0(VII)(a)
[0278] from Figure 8 It can also be seen that, Figure 8 Some exemplary glass examples presented above the line y = 0.199 + 0.0016 * x are shown, and there is no comparative example where the glass falls above the line y = 0.199 + 0.0016 * x, where y corresponds to (n d -1) / d RT And x corresponds to TiO2–La2O3. In other words, Figure 8 The exemplary glass presented herein satisfies the following equation (VII)(b), and no comparative glass satisfies the following equation (VII)(b):
[0279] (n d -1) / d RT -(0.199+0.0016*(TiO2-La2O3))>0.0(VII)(b)
[0280] Based on measurements, the exemplary embodiments presented in the figure are suitable for TiO2–La2O3 and (n d -1) / d RT In terms of combination, it is superior to the best known comparative glass with the characteristics specified in Table 11.
[0281] Table 12 below presents Figure 7 and 8Table 11 shows the comparative example glasses C7 to C17, along with numerical values for all properties specified in equations (VI)(a), (VI)(b), (VII)(a), and (VII)(b). Table 7 presents the complete composition of the comparative example glasses. Table 6 presents the complete composition of exemplary glasses derived from this disclosure, along with the properties mentioned above.
[0282] Table 12: Comparative Examples of Glasses with Properties Specified in Table 11
[0283]
[0284]
[0285] Table 12 (continued)
[0286]
[0287]
[0288] based on Figure 7 and 8 Both predicted and measured property data confirm that some exemplary glasses have a better refractive index-density ratio (“refractive power”) compared to the best comparative glass with the properties specified in Table 11. d -1) / d RT The combination of .
[0289] The following considers the compositional space, where, due to the balance between TiO2, La2O3, and B2O3, the glass exhibits a higher "refractive power" (n) at lower differences (TiO2-La2O3) (including higher negative values, such as less than or equal to -2.0 mol%, or less than or equal to -3.0 mol%, or even less than or equal to -4.0 mol%). d -1) / d RT These glasses with higher La2O3 content still possess the following characteristics: lower density at high refractive index, high transmittance, and acceptable high glass-forming ability.
[0290] Figure 9 The difference in TiO2–La2O3 and the refractive power parameter P are shown for some exemplary glasses and some comparative glasses. ref The relationship diagram is shown. Exemplary glasses (solid circles) are Examples 1, 2, 4, 5, 8 to 15, 18 to 20, 22, 24, 25, 30, 35 to 40, 45, and 50 from Table 6. Comparative example glasses (hollow circles) are Examples C7, C12, and C18 to C25 from Table 7. The refractive power parameter P, which predicts the refractive index-density ratio (“refractive power”), is determined according to Equation (III).ref . Figure 9 All exemplary and comparative glass examples shown have the characteristics specified in Table 13. In Table 13, the term "no limitation" means that it is not considered a limitation when selecting the composition.
[0291] Table 13: Figure 9 and 10 Limitations of the glass composition shown
[0292]
[0293]
[0294] The comparative glass examples listed above were selected from known glasses that, among those exhibiting the characteristics specified in Table 13, possessed the highest refractive power parameter P while having a comparable TiO2–La2O3 difference. ref .
[0295] Figure 9 The line shown corresponding to the equation y = 0.199 + 0.0025*x provides a visual representation of the differences between comparative example glass with the properties specified in Table 13 and exemplary glasses 1, 2, 4, 5, 8 to 15, 18 to 20, 22, 24, 25, 30, 35 to 40, 45, and 50. Figure 9 It can be seen that, Figure 9 The exemplary glass (solid circle) mentioned in the text falls above the line y = 0.199 + 0.0025*x, and there is no comparative example glass (hollow circle) falling above the line y = 0.199 + 0.0025*x, where y corresponds to the refractive power parameter P. ref And x corresponds to the difference between TiO2 and La2O3. In other words, Figure 9 Some of the exemplary glasses presented satisfy the following equation (VIII)(a), and there is no comparative glass that satisfies the following equation (VIII)(a):
[0296] P ref -(0.199+0.0025*(TiO2-La2O3))>0.0(VIII)(a)
[0297] from Figure 9 It can also be seen that, Figure 9 Some of the exemplary glass examples presented fall above the line y = 0.204 + 0.0025*x, and there is no comparative example glass falling above the line y = 0.204 + 0.0025*x, where y corresponds to the refractive power parameter P. ref And x corresponds to the difference between TiO2 and La2O3. In other words, Figure 9Some of the exemplary glasses presented satisfy the following equation (VIII)(b), and no comparative glass satisfies the following equation (VIII)(b):
[0298] P ref -(0.204+0.0025*TiO2-La2O3)>0.0(VIII)(b)
[0299] In terms of prediction, Figure 9 The exemplary embodiments presented are for TiO2–La2O3 and (n d -1) / d RT In terms of combination, it is superior to the best known comparative glass with the characteristics specified in Table 13.
[0300] Figure 10 Showing the TiO2–La2O3 difference and refractive index-density ratio (“refractive power”) of some exemplary glasses and some comparative glasses (n) d -1) / d RT The relationship diagram is shown. Exemplary glass (solid circles) are Examples 1, 2, 15, 18, 19, 24, 25 and 30 from Table 6. Comparative glass (hollow circles) are Examples C12, C21, C24 and C26 to C32 from Table 7. Figure 10 All exemplary and comparative glass examples shown have the characteristics specified in Table 13. In Table 13, the term "no limitation" means that it is not considered a limitation when selecting the composition.
[0301] The comparative glass examples listed above were selected from known glasses having the specified characteristics mentioned in Table 13, and possessing the highest measured refractive index to density ratio (“refractive power”) with a comparable TiO2–La2O3 difference. d -1) / d RT .
[0302] Figure 10 The line shown, corresponding to the equation y = 0.199 + 0.0025*x, provides a visual representation of the differences between the comparative example glass with the characteristics specified in Table 13 and exemplary glasses 1, 2, 15, 18, 19, 24, 25, and 30. Figure 10 It can be seen that, Figure 10 The exemplary glass (solid circle) mentioned in the text falls above the line y = 0.199 + 0.0025*x, and there is no comparative example glass (hollow circle) falling above the line y = 0.199 + 0.0025*x, where y corresponds to (n d -1) / d RT And x corresponds to TiO2–La2O3. In other words, Figure 10Some of the exemplary glasses presented satisfy the following equation (IX)(a), and there is no comparative glass that satisfies the following equation (IX)(a):
[0303] (n d -1) / d RT -(0.199+0.0025*(TiO2-La2O3))>0.0 (IX)(a)
[0304] from Figure 10 It can also be seen that, Figure 10 Some exemplary glass examples presented above the line y = 0.204 + 0.0025*x are shown, and there is no comparative example of glass above the line y = 0.204 + 0.0025*x, where y corresponds to (n d -1) / d RT And x corresponds to TiO2–La2O3. In other words, Figure 10 The exemplary glass presented herein satisfies the following equation (IX)(b), and no comparative glass satisfies the following equation (IX)(b):
[0305] (n d -1) / d RT -(0.204+0.0025*(TiO2-La2O3))>0.0 (IX)(b)
[0306] According to measurements, Figure 10 The exemplary embodiments presented herein are for TiO2–La2O3 and (n d -1) / d RT In terms of combination, it is superior to the best known comparative glass with the characteristics specified in Table 13.
[0307] Table 14 below presents Figure 9 and 10 Table 13 shows the comparative example glasses C7, C12, and C18 to C32, along with numerical values for all properties specified in equations (VIII)(a), (VIII)(b), (IX)(a), and (IX)(b). Table 7 presents the complete composition of the comparative example glasses. Table 6 presents the complete composition of exemplary glasses derived from this disclosure, along with the properties mentioned above.
[0308] Table 14: Comparative Examples of Glass Properties with Characteristics Specified in Table 13
[0309]
[0310]
[0311]
[0312] Table 14 (continued)
[0313]
[0314]
[0315]
[0316] based on Figure 9 and 10 Both predicted and measured property data confirm that some exemplary glasses have a better refractive index-density ratio (“refractive power”) compared to the best comparative glass with the properties specified in Table 13. d -1) / d RT The combination of .
[0317] This disclosure includes the following non-limiting aspects. To the extent not described, any feature of aspects 1 through 68 may be combined, in whole or in part, with any one or more features of other aspects of this disclosure to form additional aspects, even if such combinations are not described.
[0318] According to the first aspect, the glass contains multiple components, and the composition of the glass includes: 29.0 mol% B₂O₃ (greater than or equal to 0.5 mol%), 25.2 mol% TiO₂ (greater than or equal to 0.0 mol%), 20.0 mol% Bi₂O₃ (greater than or equal to 0.0 mol%), 20.0 mol% TeO₂ (greater than or equal to 0.0 mol%), 15.0 mol% P₂O₅ (greater than or equal to 0.0 mol%), and 10 mol% Bi₂O₃ (greater than or equal to 0.0 mol%). 0.5 mol% Nb₂O₅, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% Al₂O₃, greater than or equal to 0.0 mol% and less than or equal to 5.0 mol% MoO₃, greater than or equal to 0.0 mol% and less than or equal to 4.0 mol% V₂O₅, greater than or equal to 0.0 mol% and less than or equal to 2.5 mol% GeO₂, greater than or equal to 0.0 mol% and less than or equal to 2.5 mol% ZnO, greater than or equal to 0.0 mol% and less than or equal to 1.0 mol% Ta₂O₅, greater than or equal to 95.0 mol% R m O n , greater than or equal to 0.0 mol% and less than or equal to 29.0 mol% RE m O nThe composition of the glass is greater than or equal to 10.0 mol% SiO2+B2O3+P2O5, less than or equal to 34.0 mol% SiO2+B2O3, greater than or equal to 0.3 mol% CaO+SrO+BaO+Y2O3, and greater than or equal to 0.0 mol% and less than or equal to 25.0 mol% R2O+RO, wherein the composition satisfies the following condition: Y2O3-Gd2O3 [mol%] ≥ -2.0, and the glass satisfies the following condition: 4.0 ≤ P d ≤6.0 and P n -(1.207+0.155*P d )>0.000, where P n It is the refractive index parameter, calculated as a mole percent of the components in the glass composition according to the following equation (I):
[0319] P n =1.844+0.0054162*La2O3+0.0031113*TiO2-0.004212*B2O3-0.0035692*SiO2+0.0027887*ZrO2+0.0078026* Nb2O5-0.00012928*CaO+0.00076566*BaO+0.0043601*Y2O3+0.00067408*ZnO+0.0068029*Gd2O3-0.0025106*N a2O+0.0039937*WO3-0.0043208*Al2O3-0.0011666*Li2O+0.0051727*PbO+0.012958*Bi2O3-0.0018753*GeO2- 0.0014084*TeO2+0.0086647*Er2O3+0.0097345*Yb2O3-0.0038734*K2O-0.00041776*SrO-0.0017294*MgO, (I)
[0320] P d It is a density parameter, calculated as the molar percentage of the components in the glass composition according to the following equation (II):
[0321] P d=4.276+0.058714*La2O3-0.0077783*TiO2-0.023741*B2O3-0.018272*SiO2+0.010913*ZrO2-0.00 14478*CaO+0.023857*BaO+0.033560*Y2O3+0.010174*ZnO+0.082094*Gd2O3-0.008237*Na2O+0.03 5497*WO3-0.031171*Al2O3-0.0080004*Li2O+0.051830*PbO+0.10437*Bi2O3-0.012816*GeO2-0.0 065609*TeO2+0.10060*Er2O3+0.10637*Yb2O3-0.017097*K2O+0.009821*SrO-0.0037906*MgO, (II)
[0322] In the formula, R m O n It is the sum of all oxides, RE m O n R₂O is the sum of rare earth metal oxides, R₂O is the sum of monovalent metal oxides, RO is the sum of divalent metal oxides, and the asterisk (*) represents the multiplication sign.
[0323] According to the second aspect, the glass of the first aspect, wherein the glass has a density greater than or equal to 4.0 g / cm³. 3 And less than or equal to 6.0 g / cm³ 3 room temperature density d RT And among them, the glass satisfies the following condition: n d -(1.207+0.155*d RT )>0.000, where n d It is the refractive index at 587.56 nm.
[0324] According to aspect 3, the glass in any of aspects 1-2 satisfies the following condition: n d -(1.217+0.155*d RT )>0.000, where n d It is the refractive index at 587.56 nm, d RT [g / cm 3 [ ] is the density at room temperature.
[0325] According to aspect 4, the glass in any of aspects 1-3 satisfies the following condition: P n -(1.217+0.155*P d )>0.000.
[0326] According to aspect 5, the glass of any one of aspects 1-4, wherein the composition comprises: greater than or equal to 20.0 mol% and less than or equal to 25.2 mol% TiO2, greater than or equal to 15.0 mol% and less than or equal to 29.0 mol% La2O3, greater than or equal to 15.0 mol% and less than or equal to 22.5 mol% B2O3, greater than or equal to 5.0 mol% and less than or equal to 20.0 mol% SiO2, and greater than or equal to 4.0 mol% and less than or equal to 9.0 mol% Zr O2, greater than or equal to 2.5 mol% and less than or equal to 10.0 mol% Nb2O5, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% BaO, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% CaO, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% Ga2O3, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% Y2O3, and greater than or equal to 0.0 mol% and less than or equal to 2.0 mol% WO3.
[0327] According to aspect 6, the glass of any one of aspects 1-5, wherein the composition comprises one or more of the following: greater than or equal to 20.25 mol% and less than or equal to 25.2 mol% TiO2, greater than or equal to 20.0 mol% and less than or equal to 27.5 mol% La2O3, greater than or equal to 16.4 mol% and less than or equal to 20.4 mol% B2O3, greater than or equal to 10.0 mol% and less than or equal to 17.5 mol% SiO2, greater than or equal to 5.3 mol% and less than or equal to 8.1 mol% ZrO2, greater than or equal to 4.5 mol% and less than or equal to 9.3 mol% Nb2O5, greater than or equal to The following concentrations are included: Y₂O₃ (0.5 mol% and less than or equal to 6.3 mol%), CaO (0.0 mol% and less than or equal to 9.0 mol%), Ga₂O₃ (0.0 mol% and less than or equal to 8.0 mol%), BaO (0.0 mol% and less than or equal to 6.5 mol%), WO₃ (0.0 mol% and less than or equal to 1.8 mol%), Gd₂O₃ (0.0 mol% and less than or equal to 1.35 mol%), SrO (0.0 mol% and less than or equal to 0.9 mol%), and Yb₂O₃ (0.0 mol% and less than or equal to 0.9 mol%).
[0328] According to aspect 7, the glass of any one of aspects 1-6, wherein the composition comprises: greater than or equal to 21.0 mol% and less than or equal to 26.3 mol% La₂O₃, greater than or equal to 20.25 mol% and less than or equal to 25.2 mol% TiO₂, greater than or equal to 16.9 mol% and less than or equal to 20.4 mol% B₂O₃, greater than or equal to 11.0 mol% and less than or equal to 16.5 mol% SiO₂, greater than or equal to 5.6 mol% and less than or equal to 8.0 mol% ZrO₂, greater than or equal to 5.1 mol% and less than or equal to 8.6 mol% Nb₂O₅, greater than or equal to 0.7 5 mol% and less than or equal to 5.50 mol% Y₂O₃, greater than or equal to 0.0 mol% and less than or equal to 8.0 mol% CaO, greater than or equal to 0.0 mol% and less than or equal to 7.5 mol% Ga₂O₃, greater than or equal to 0.0 mol% and less than or equal to 5.5 mol% BaO, greater than or equal to 0.0 mol% and less than or equal to 1.6 mol% WO₃, greater than or equal to 0.0 mol% and less than or equal to 1.2 mol% Gd₂O₃, greater than or equal to 0.0 mol% and less than or equal to 0.8 mol% SrO, and greater than or equal to 0.0 mol% and less than or equal to 0.8 mol% Yb₂O₃.
[0329] According to aspect 8, for any of aspects 1-7, the glass wherein the composition satisfies one or more of the following conditions: the sum of La2O3+TiO2+B2O3+SiO2+ZrO2+Nb2O5+BaO+Y2O3+CaO+Ga2O3+Gd2O3+ZnO+WO3+CeO2+SrO+Na2O+Ta2O5+Al2O3 is greater than or equal to 99.0 mol%, and the sum of La2O3+Y2O3+Gd2O3+ZnO+WO3+CeO2+SrO+Na2O+Ta2O5+Al2O3 is greater than or equal to 99.0 mol%. The sum of d2O3+TiO2+B2O3+SiO2+ZrO2+Nb2O5 is greater than or equal to 99.0 mol%, the sum of La2O3+Y2O3+Gd2O3+TiO2+B2O3+SiO2+ZrO2+Nb2O5+CaO+BaO is greater than or equal to 99.0 mol%, and the sum of La2O3+TiO2+B2O3+SiO2+ZrO2+Nb2O5 is greater than or equal to 97.0 mol%.
[0330] According to aspect 9, a glass of any one of aspects 1-8, wherein the composition comprises: greater than or equal to 5.0 mol% B2O3, greater than or equal to 5.0 mol% La2O3, greater than or equal to 5.0 mol% Nb2O5, greater than or equal to 5.0 mol% SiO2, greater than or equal to 5.0 mol% TiO2, and greater than or equal to 1.0 mol% ZrO2+HfO2.
[0331] According to aspect 10, the glass of any one of aspects 1-9, wherein the composition comprises greater than or equal to 0.0 mol% and less than or equal to 6.0 mol% R2O+RO.
[0332] According to the 11th aspect, the glass of the 10th aspect, wherein the component composition contains greater than or equal to 0.0 mol% and less than or equal to 1.0 mol% R2O+RO.
[0333] According to aspect 12, the glass of any one of aspects 1-11, wherein the composition satisfies the following condition: 0.00≤SiO2 / (SiO2+B2O3)[mol%]≤0.40.
[0334] According to aspect 13, the glass of any one of aspects 1-12, wherein the composition satisfies the following condition: 0.38≤SiO2 / (SiO2+B2O3)[mol%]≤0.75.
[0335] According to aspect 14, a glass of any one of aspects 1-13, wherein the composition comprises: greater than or equal to 0.0 mol% and less than or equal to 6.5 mol% CaO, and greater than or equal to 0.0 mol% and less than or equal to 5.5 mol% BaO, and wherein the composition is substantially free of ZnO.
[0336] According to aspect 15, a glass of any one of aspects 1-14, wherein the composition comprises: greater than or equal to 0.0 mol% and less than or equal to 5.0 mol% Y₂O₃, greater than or equal to 0.0 mol% and less than or equal to 2.0 mol% TeO₂, greater than or equal to 0.0 mol% and less than or equal to 0.5 mol% GeO₂, greater than or equal to 0.0 mol% and less than or equal to 0.5 mol% PbO, greater than or equal to 0.0 mol% and less than or equal to 0.2 mol% As₂O₃, and greater than or equal to 0.0 mol% and less than or equal to 0.2 mol% Sb₂O₃, and wherein the composition is substantially free of fluorine and substantially free of V₂O₅.
[0337] According to aspect 16, a glass of any one of aspects 1-15, wherein the composition comprises: greater than or equal to 22.0 mol% and less than or equal to 25.0 mol% TiO2, greater than or equal to 20.0 mol% and less than or equal to 29.0 mol% La2O3, greater than or equal to 16.0 mol% and less than or equal to 20.0 mol% B2O3, greater than or equal to 10.0 mol% and less than or equal to 20.0 mol% SiO2, and greater than or equal to 6.5 mol% and less than or equal to 8.0 mol% ZnO2. rO2, greater than or equal to 5.0 mol% and less than or equal to 6.7 mol% Nb2O5, greater than or equal to 0.0 mol% and less than or equal to 6.0 mol% Y2O3, greater than or equal to 0.0 mol% and less than or equal to 3.0 mol% BaO, greater than or equal to 0.0 mol% and less than or equal to 2.0 mol% Gd2O3, and greater than or equal to 98.0 mol% TiO2+La2O3+B2O3+SiO2+ZrO2+Nb2O5+Y2O3+BaO+Gd2O3.
[0338] According to aspect 17, the glass of any one of aspects 1-16, wherein the glass satisfies the following condition: 4.5 g / cm³ 3 ≤P d ≤5.5g / cm 3 and 1.95≤P n ≤2.07, where P n It is the refractive index parameter, calculated as a mole percent of the components in the glass composition according to the following equation (I):
[0339] P n =1.844+0.0054162*La2O3+0.0031113*TiO2-0.004212*B2O3-0.0035692*SiO2+0.0027887*ZrO2+0.0078026* Nb2O5-0.00012928*CaO+0.00076566*BaO+0.0043601*Y2O3+0.00067408*ZnO+0.0068029*Gd2O3-0.0025106*N a2O+0.0039937*WO3-0.0043208*Al2O3-0.0011666*Li2O+0.0051727*PbO+0.012958*Bi2O3-0.0018753*GeO2- 0.0014084*TeO2+0.0086647*Er2O3+0.0097345*Yb2O3-0.0038734*K2O-0.00041776*SrO-0.0017294*MgO, (I)
[0340] P dIt is a density parameter, calculated as the molar percentage of the components in the glass composition according to the following equation (II):
[0341] P d =4.276+0.058714*La2O3-0.0077783*TiO2-0.023741*B2O3-0.018272*SiO2+0.010913*ZrO2-0.00 14478*CaO+0.023857*BaO+0.033560*Y2O3+0.010174*ZnO+0.082094*Gd2O3-0.008237*Na2O+0.03 5497*WO3-0.031171*Al2O3-0.0080004*Li2O+0.051830*PbO+0.10437*Bi2O3-0.012816*GeO2-0.0 065609*TeO2+0.10060*Er2O3+0.10637*Yb2O3-0.017097*K2O+0.009821*SrO-0.0037906*MgO, (II)
[0342] According to aspect 18, the glass of any one of aspects 1-17, wherein the glass has a density greater than or equal to 4.5 g / cm³. 3 And less than or equal to 5.5 g / cm 3 room temperature density d RT and a refractive index n at 587.56 nm that is greater than or equal to 1.95 and less than or equal to 2.07. d .
[0343] According to aspect 19, a glass of any one of aspects 1-18, wherein when cooled in air from 1100°C to 500°C in 2.5 minutes, the glass does not crystallize.
[0344] According to aspect 20, a glass of any one of aspects 1-19, wherein, when the thickness is 10 mm, the glass has a transmittance TX of greater than or equal to 70% at a wavelength of 460 nm. 460 nm .
[0345] According to aspect 21, a method for manufacturing an optical element, the method comprising processing glass according to any one of aspects 1-20.
[0346] According to aspect 22, optical elements of glass including any one of aspects 1-21.
[0347] According to aspect 23, the glass contains multiple components, and the composition of the glass includes: greater than or equal to 1.0 mol% and less than or equal to 40.0 mol% TiO2, greater than or equal to 1.0 mol% and less than or equal to 40.0 mol% B2O3, greater than or equal to 0.0 mol% and less than or equal to 35.0 mol% SiO2, greater than or equal to 0.0 mol% and less than or equal to 30.0 mol% La2O3, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% ZrO2, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% GeO2, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% Al2O3, and greater than or equal to 0 mol% and less than or equal to 6.8 mol% Nb2O5. The glass may contain, and optionally, one or more components selected from the group consisting of: greater than or equal to 0.0 mol% and less than or equal to 6.7 mol% Y₂O₃, greater than or equal to 0.0 mol% and less than or equal to 25.0 mol% RO, greater than or equal to 0.0 mol% and less than or equal to 25.0 mol% R₂O, greater than or equal to 45.3 mol% La₂O₃+Y₂O₃+Gd₂O₃+TiO₂, greater than or equal to 12.1 mol% Nb₂O₅+ZrO₂, and may optionally contain one or more components selected from the group consisting of: Bi₂O₃, Er₂O₃, Nd₂O₃, WO₃ and Yb₂O₃, wherein the composition of the components satisfies the following conditions: SiO₂+B₂O₃-TiO₂[mol%]≥7.05 and B₂O₃-SiO₂[mol%]≤7.0, and the glass satisfies the following condition: P ref -(0.196+0.0016*(TiO2-La2O3))>0.000, where P ref It is a refractive power parameter, calculated as the molar percentage of the components in the glass composition according to the following equation (III):
[0348] P ref (cm 3 / g)=0.201656+0.00018225*B2O3-0.0010873*BaO-0.0024853*Bi2O3-0.0030326*Er2O3-0.0018856*Gd2O3-0.0017563*La2O3-0.0002505*Na2O+0.0017526*N b2O5-0.0025472*Nd2O3-0.0016439*PbO+0.000050096*SiO2+0.0011794*TiO2- 0.00072112*WO3-0.00079167*Y2O3-0.0031015*Yb2O3-0.00034209*ZnO, (III)
[0349] In the formula, RO is the sum of divalent metal oxides, R2O is the sum of monovalent metal oxides, and the symbol (*) represents the multiplication sign.
[0350] According to aspect 24, glass in aspect 23, wherein the glass satisfies the following condition: (n d -1) / d RT -(0.196+0.0016*(TiO2-La2O3))>0.000, where n d It is the refractive index at 587.56 nm, and d RT (g / cm 3 () is the density at room temperature.
[0351] According to aspect 25, glass in aspect 24, wherein the glass satisfies the following condition: (n d -1) / d RT -(0.199+0.0016*(TiO2-La2O3))>0.000.
[0352] According to aspect 26, the glass of any one of aspects 23-25, wherein the glass satisfies the following condition: P ref -(0.199+0.0016*(TiO2-La2O3))>0.000.
[0353] According to aspect 27, the glass of any one of aspects 23-26, wherein the composition comprises: greater than or equal to 20.0 mol% and less than or equal to 27.5 mol% TiO2, greater than or equal to 15.0 mol% and less than or equal to 30.0 mol% La2O3, greater than or equal to 15.0 mol% and less than or equal to 22.5 mol% B2O3, greater than or equal to 5.0 mol% and less than or equal to 20.0 mol% SiO2, and greater than or equal to 4.0 mol% and less than or equal to 9.0 mol%. % ZrO2, greater than or equal to 2.5 mol% and less than or equal to 6.8 mol% Nb2O5, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% BaO, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% CaO, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% Ga2O3, greater than or equal to 0.0 mol% and less than or equal to 4.0 mol% ZnO, and greater than or equal to 0.0 mol% and less than or equal to 2.0 mol% WO3.
[0354] According to aspect 28, the glass of any one of aspects 23-27, wherein the composition comprises one or more of the following: greater than or equal to 20.25 mol% and less than or equal to 26.00 mol% TiO2, greater than or equal to 20.0 mol% and less than or equal to 27.5 mol% La2O3, greater than or equal to 16.4 mol% and less than or equal to 20.4 mol% B2O3, greater than or equal to 10.0 mol% and less than or equal to 17.5 mol% SiO2, greater than or equal to 5.3 mol% and less than or equal to 8.1 mol% ZrO2, greater than or equal to 4.5 mol% and less than or equal to 6.8 mol% Nb2O5, greater than or equal to 0.5 ...27.5 mol% La2O3, greater than or equal to 27.5 mol% La2O3, greater than or equal to 27.5 mol% La2O3, greater than or equal to 27.5 mol% La2O3, greater than or equal to 27.5 mol% La2O3, greater than or equal to 27.5 mol% La The following are included: 6.3 mol% Y₂O₃, greater than or equal to 0.0 mol% and less than or equal to 9.0 mol% CaO, greater than or equal to 0.0 mol% and less than or equal to 8.0 mol% Ga₂O₃, greater than or equal to 0.0 mol% and less than or equal to 6.5 mol% BaO, greater than or equal to 0.0 mol% and less than or equal to 3.0 mol% ZnO, greater than or equal to 0.0 mol% and less than or equal to 1.8 mol% WO₃, greater than or equal to 0 mol% and less than or equal to 1.35 mol% Gd₂O₃, greater than or equal to 0.0 mol% and less than or equal to 0.9 mol% SrO, and greater than or equal to 0.0 mol% and less than or equal to 0.9 mol% Yb₂O₃.
[0355] According to aspect 29, a glass of any one of aspects 23-28, wherein the composition comprises: greater than or equal to 21.0 mol% and less than or equal to 26.3 mol% La2O3, greater than or equal to 20.25 mol% and less than or equal to 25.50 mol% TiO2, greater than or equal to 16.9 mol% and less than or equal to 20.4 mol% B2O3, greater than or equal to 11.0 mol% and less than or equal to 16.5 mol% SiO2, greater than or equal to 5.6 mol% and less than or equal to 8.0 mol% ZrO2, greater than or equal to 5.1 mol% and less than or equal to 6.8 mol% Nb2O5, and greater than or equal to 0.75 mol% and less than or equal to 5. 50 mol% Y₂O₃, greater than or equal to 0.0 mol% and less than or equal to 8.0 mol% CaO, greater than or equal to 0.0 mol% and less than or equal to 7.5 mol% Ga₂O₃, greater than or equal to 0.0 mol% and less than or equal to 5.5 mol% BaO, greater than or equal to 0.0 mol% and less than or equal to 2.7 mol% ZnO, greater than or equal to 0.0 mol% and less than or equal to 1.6 mol% WO₃, greater than or equal to 0.0 mol% and less than or equal to 1.2 mol% Gd₂O₃, greater than or equal to 0.0 mol% and less than or equal to 0.8 mol% SrO, and greater than or equal to 0.0 mol% and less than or equal to 0.8 mol% Yb₂O₃.
[0356] According to aspect 30, the glass of any one of aspects 23-29, wherein the composition satisfies one or more of the following conditions: the sum of La2O3+TiO2+B2O3+SiO2+ZrO2+Nb2O5+BaO+Y2O3+CaO+Ga2O3+Gd2O3+ZnO+WO3+CeO2+SrO+Na2O+Ta2O5+Al2O3 is greater than or equal to 99.0 mol%, and the sum of La2O3+Y2O3+ The sum of Gd₂O₃+TiO₂+B₂O₃+SiO₂+ZrO₂+Nb₂O₅ is greater than or equal to 99.0 mol%, the sum of La₂O₃+Y₂O₃+Gd₂O₃+TiO₂+B₂O₃+SiO₂+ZrO₂+Nb₂O₅+CaO+BaO is greater than or equal to 99.0 mol%, and the sum of La₂O₃+TiO₂+B₂O₃+SiO₂+ZrO₂+Nb₂O₅ is greater than or equal to 97.0 mol%.
[0357] According to aspect 31, a glass of any one of aspects 23-30, wherein the composition comprises: greater than or equal to 5.0 mol% B2O3, greater than or equal to 5.0 mol% La2O3, greater than or equal to 5.0 mol% Nb2O5, greater than or equal to 5.0 mol% SiO2, greater than or equal to 5.0 mol% TiO2, greater than or equal to 1.0 mol% ZrO2+HfO2, and greater than or equal to 10.0 mol% SiO2+B2O3.
[0358] According to aspect 32, the glass of any one of aspects 23-31, wherein the composition comprises greater than or equal to 0.0 mol% and less than or equal to 6.0 mol% R2O+RO.
[0359] According to aspect 33, the glass of aspect 32, wherein the component composition contains greater than or equal to 0.0 mol% and less than or equal to 1.0 mol% R2O+RO.
[0360] According to aspect 34, the glass of any one of aspects 23-33, wherein the composition satisfies the following condition: 0.00≤SiO2 / (SiO2+B2O3)[mol%]≤0.40.
[0361] According to aspect 35, the glass of any one of aspects 23-34, wherein the composition satisfies the following condition: 0.38≤SiO2 / (SiO2+B2O3)[mol%]≤0.75.
[0362] According to aspect 36, a glass of any one of aspects 23-35, wherein the composition comprises: greater than or equal to 0.0 mol% and less than or equal to 6.5 mol% CaO, and greater than or equal to 0.0 mol% and less than or equal to 5.5 mol% BaO, and wherein the composition is substantially free of ZnO.
[0363] According to aspect 37, a glass of any one of aspects 23-36, wherein the composition comprises: greater than or equal to 0.0 mol% and less than or equal to 5.0 mol% Y₂O₃, greater than or equal to 0.0 mol% and less than or equal to 2.0 mol% Ta₂O₅, greater than or equal to 0.0 mol% and less than or equal to 2.0 mol% TeO₂, greater than or equal to 0.0 mol% and less than or equal to 0.5 mol% GeO₂, greater than or equal to 0.0 mol% and less than or equal to 0.5 mol% PbO, greater than or equal to 0.0 mol% and less than or equal to 0.2 mol% As₂O₃, and greater than or equal to 0.0 mol% and less than or equal to 0.2 mol% Sb₂O₃, and wherein the composition is substantially free of fluorine and substantially free of V₂O₅.
[0364] According to aspect 38, a glass of any one of aspects 23-28 and 30-37, wherein the composition comprises: greater than or equal to 22.0 mol% and less than or equal to 25.0 mol% TiO2, greater than or equal to 20.0 mol% and less than or equal to 30.0 mol% La2O3, greater than or equal to 16.0 mol% and less than or equal to 20.0 mol% B2O3, greater than or equal to 10.0 mol% and less than or equal to 20.0 mol% SiO2, and greater than or equal to 6.5 mol% and less than or equal to 8.0 mol%. The following are the molar percentages of ZrO2, Nb2O5, Y2O3, BaO, Gd2O3, and TiO2+La2O3+B2O3+SiO2+ZrO2+Nb2O5+Y2O3+BaO+Gd2O3: ≥5.0 mol% and ≤6.7 mol%; ≥0.0 mol% and ≤6.0 mol%; ≥0.0 mol% and ≤2.0 mol%; and ≥98.0 mol% of TiO2+La2O3+B2O3+SiO2+ZrO2+Nb2O5+Y2O3+BaO+Gd2O3: ≥98.0 mol%
[0365] According to aspect 39, glass of any one of aspects 23-38, wherein the glass satisfies the following condition: 4.5 g / cm³ 3 ≤P d ≤5.5g / cm 3 and 1.95≤P n ≤2.07, where P n It is the refractive index parameter, calculated as a mole percent of the components in the glass composition according to the following equation (I):
[0366] P n =1.844+0.0054162*La2O3+0.0031113*TiO2-0.004212*B2O3-0.0035692*SiO2+0.0027887*ZrO2+0.0078026* Nb2O5-0.00012928*CaO+0.00076566*BaO+0.0043601*Y2O3+0.00067408*ZnO+0.0068029*Gd2O3-0.0025106*N a2O+0.0039937*WO3-0.0043208*Al2O3-0.0011666*Li2O+0.0051727*PbO+0.012958*Bi2O3-0.0018753*GeO2- 0.0014084*TeO2+0.0086647*Er2O3+0.0097345*Yb2O3-0.0038734*K2O-0.00041776*SrO-0.0017294*MgO, (I)
[0367] P d It is a density parameter, calculated as the molar percentage of the components in the glass composition according to the following equation (II):
[0368] P d =4.276+0.058714*La2O3-0.0077783*TiO2-0.023741*B2O3-0.018272*SiO2+0.010913*ZrO2-0.00 14478*CaO+0.023857*BaO+0.033560*Y2O3+0.010174*ZnO+0.082094*Gd2O3-0.008237*Na2O+0.03 5497*WO3-0.031171*Al2O3-0.0080004*Li2O+0.051830*PbO+0.10437*Bi2O3-0.012816*GeO2-0.0 065609*TeO2+0.10060*Er2O3+0.10637*Yb2O3-0.017097*K2O+0.009821*SrO-0.0037906*MgO, (II)
[0369] According to aspect 40, the glass of any one of aspects 23-39, wherein the glass has a density greater than or equal to 4.5 g / cm³. 3 And less than or equal to 5.5 g / cm 3 room temperature density d RT and a refractive index n at 587.56 nm that is greater than or equal to 1.95 and less than or equal to 2.07.d .
[0370] According to aspect 41, a glass of any one of aspects 23-40, wherein the glass has a liquidus temperature T less than or equal to 1260°C. liq .
[0371] According to aspect 42, a glass of any one of aspects 23-41, wherein the glass does not crystallize when cooled from 1100°C to 500°C in air over 2.5 minutes.
[0372] According to aspect 43, a glass of any one of aspects 23-42, wherein, when the thickness is 10 mm, the glass has a transmittance TX greater than or equal to 70% at a wavelength of 460 nm. 460 nm .
[0373] According to aspect 44, a method for manufacturing an optical element, the method comprising processing the glass of any one of aspects 23-43.
[0374] According to aspect 45, optical elements of glass including any of aspects 23-44.
[0375] According to aspect 46, the glass contains multiple components, and the composition of the glass includes: greater than or equal to 1.0 mol% and less than or equal to 40.0 mol% TiO2, greater than or equal to 1.0 mol% and less than or equal to 40.0 mol% B2O3, greater than or equal to 0.0 mol% and less than or equal to 35.0 mol% SiO2, greater than or equal to 0.0 mol% and less than or equal to 30.0 mol% La2O3, greater than or equal to 0.0 mol% and less than or equal to 20.0 mol% CaO, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% ZrO2, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% GeO2, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% Al2O3, greater than or equal to 0 mol% and less than or equal to 6.75 mol% Nb2O5, and greater than or equal to 0.0 mol% and less than or equal to 5.5 mol%. The glass may optionally contain one or more components selected from the group consisting of: Bi2O3, Er2O3, and Nd2O3, wherein the composition satisfies the following conditions: TiO2-B2O3 [mol%] ≥ -6.0 and TiO2-La2O3 [mol%] ≤ 5.0, and the glass satisfies the following condition: P ref -(0.199+0.0025*(TiO2-La2O3))>0.000, where P ref It is a refractive power parameter, calculated as the molar percentage of the components in the glass composition according to the following equation (III):
[0376] P ref=0.201656+0.00018225*B2O3-0.0010873*BaO-0.0024853*Bi2O3-0.0030326* Er2O3-0.0018856*Gd2O3-0.0017563*La2O3-0.0002505*Na2O+0.0017526*Nb2 O5-0.0025472*Nd2O3-0.0016439*PbO+0.000050096*SiO2+0.0011794*TiO2-0 .00072112*WO3-0.00079167*Y2O3-0.0031015*Yb2O3-0.00034209*ZnO, (III)
[0377] In the formula, RO is the sum of divalent metal oxides, R2O is the sum of monovalent metal oxides, and the symbol (*) represents the multiplication sign.
[0378] According to aspect 47, glass in aspect 46, wherein the glass satisfies the following condition: (n d -1) / d RT -(0.199+0.0025*(TiO2-La2O3))>0.000, where n d It is the refractive index at 587.56 nm, and d RT (g / cm 3 () is the density at room temperature.
[0379] According to aspect 48, the glass in any of aspects 46-47 satisfies the following condition: (n d -1) / d RT -(0.204+0.0025*(TiO2-La2O3))>0.000, where n d It is the refractive index at 587.56 nm, and d RT (g / cm 3 () is the density at room temperature.
[0380] According to aspect 49, the glass in any of aspects 46-48 satisfies the following condition: P ref -(0.204+0.0025*(TiO2-La2O3))>0.000.
[0381] According to aspect 50, a glass of any one of aspects 46-49, wherein the composition comprises: greater than or equal to 20.0 mol% and less than or equal to 27.5 mol% TiO2, greater than or equal to 15.0 mol% and less than or equal to 30.0 mol% La2O3, greater than or equal to 15.0 mol% and less than or equal to 22.5 mol% B2O3, greater than or equal to 5.0 mol% and less than or equal to 20.0 mol% SiO2, greater than or equal to 4.0 mol% and less than or equal to 9.0 mol% ZrO2, greater than or equal to 2.5 mol% and less than or equal to 6.8 mol% Nb2O5, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% CaO, and greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% Ga2O3.
[0382] According to aspect 51, a glass of any one of aspects 46-50, wherein the composition comprises one or more of the following: greater than or equal to 20.25 mol% and less than or equal to 26.00 mol% TiO2, greater than or equal to 20.0 mol% and less than or equal to 27.5 mol% La2O3, greater than or equal to 16.4 mol% and less than or equal to 20.4 mol% B2O3, greater than or equal to 10.0 mol% and less than or equal to 17.5 mol% SiO2, greater than or equal to 5.3 mol% and less than or equal to 8.1 mol% ZrO2, greater than or equal to 4.5 mol% and less than or equal to 6.8 mol% Nb₂O₅, greater than or equal to 0.5 mol% and less than or equal to 4.6 mol% Y₂O₃, greater than or equal to 0.0 mol% and less than or equal to 9.0 mol% CaO, greater than or equal to 0.0 mol% and less than or equal to 8.0 mol% Ga₂O₃, greater than or equal to 0.0 mol% and less than or equal to 3.0 mol% ZnO, greater than or equal to 0 mol% and less than or equal to 1.35 mol% Gd₂O₃, greater than or equal to 0.0 mol% and less than or equal to 0.9 mol% SrO, and greater than or equal to 0.0 mol% and less than or equal to 0.9 mol% Yb₂O₃.
[0383] According to aspect 52, a glass of any one of aspects 46-51, wherein the composition comprises: greater than or equal to 21.0 mol% and less than or equal to 26.3 mol% La₂O₃, greater than or equal to 20.25 mol% and less than or equal to 25.50 mol% TiO₂, greater than or equal to 16.9 mol% and less than or equal to 20.4 mol% B₂O₃, greater than or equal to 11.0 mol% and less than or equal to 16.5 mol% SiO₂, greater than or equal to 5.6 mol% and less than or equal to 8.0 mol% ZrO₂, and greater than or equal to 5.1 mol% and less than or equal to 6.8 mol%. The following are the percentages of Nb₂O₅, Y₂O₃, CaO, Ga₂O₃, ZnO, Gd₂O₃, SrO, and Yb₂O₃: 0.0 mol% and 0.8 mol% of Nb₂O₅, Y₂O₃, Gd₂O₃, SrO, and SrO: 0.0 mol% and 0.8 mol% of Gd₂O₃.
[0384] According to aspect 53, the glass of any one of aspects 46-52, wherein the composition satisfies one or more of the following conditions: the sum of La2O3+TiO2+B2O3+SiO2+ZrO2+Nb2O5+BaO+Y2O3+CaO+Ga2O3+Gd2O3+ZnO+WO3+CeO2+SrO+Na2O+Ta2O5+Al2O3 is greater than or equal to 99.0 mol%, and the sum of La2O3+Y2O3+ The sum of Gd₂O₃+TiO₂+B₂O₃+SiO₂+ZrO₂+Nb₂O₅ is greater than or equal to 99.0 mol%, the sum of La₂O₃+Y₂O₃+Gd₂O₃+TiO₂+B₂O₃+SiO₂+ZrO₂+Nb₂O₅+CaO+BaO is greater than or equal to 99.0 mol%, and the sum of La₂O₃+TiO₂+B₂O₃+SiO₂+ZrO₂+Nb₂O₅ is greater than or equal to 97.0 mol%.
[0385] According to aspect 54, a glass of any one of aspects 46-53, wherein the composition comprises: greater than or equal to 5.0 mol% B2O3, greater than or equal to 5.0 mol% La2O3, greater than or equal to 5.0 mol% Nb2O5, greater than or equal to 5.0 mol% SiO2, greater than or equal to 5.0 mol% TiO2, greater than or equal to 1.0 mol% ZrO2+HfO2, and greater than or equal to 10.0 mol% SiO2+B2O3.
[0386] According to aspect 55, the glass of any one of aspects 46-54, wherein the composition comprises greater than or equal to 0.0 mol% and less than or equal to 6.0 mol% R2O+RO.
[0387] According to aspect 56, the glass of aspect 55, wherein the composition comprises greater than or equal to 0.0 mol% and less than or equal to 1.0 mol% R2O+RO.
[0388] According to aspect 57, a glass of any one of aspects 46-56, wherein the composition satisfies the following condition: 0.00≤SiO2 / (SiO2+B2O3)[mol%]≤0.40.
[0389] According to aspect 58, the glass of any one of aspects 46-57, wherein the composition satisfies the following condition: 0.38≤SiO2 / (SiO2+B2O3)[mol%]≤0.75.
[0390] According to aspect 59, a glass of any one of aspects 46-58, wherein the composition comprises 0.0 mol% and less than 6.5 mol% CaO, and wherein the composition is substantially free of ZnO.
[0391] According to aspect 60, a glass of any one of aspects 46-59, wherein the composition comprises: greater than or equal to 0.0 mol% and less than or equal to 2.0 mol% Ta2O5, greater than or equal to 0.0 mol% and less than or equal to 2.0 mol% TeO2, greater than or equal to 0.0 mol% and less than or equal to 0.5 mol% GeO2, greater than or equal to 0.0 mol% and less than or equal to 0.5 mol% PbO, greater than or equal to 0.0 mol% and less than or equal to 0.2 mol% As2O3, and greater than or equal to 0.0 mol% and less than or equal to 0.2 mol% Sb2O3, and wherein the composition is substantially free of fluorine and substantially free of V2O5.
[0392] According to aspect 61, a glass of any one of aspects 46-60, wherein the composition comprises: greater than or equal to 22.0 mol% and less than or equal to 25.0 mol% TiO2, greater than or equal to 20.0 mol% and less than or equal to 30.0 mol% La2O3, greater than or equal to 16.0 mol% and less than or equal to 20.0 mol% B2O3, greater than or equal to 10.0 mol% and less than or equal to 20.0 mol% SiO2, and greater than or equal to 6. 5 mol% and less than or equal to 8.0 mol% ZrO2, greater than or equal to 5.0 mol% and less than or equal to 6.7 mol% Nb2O5, greater than or equal to 0.0 mol% and less than or equal to 3.0 mol% BaO, greater than or equal to 0.0 mol% and less than or equal to 2.0 mol% Gd2O3, and greater than or equal to 98.0 mol% TiO2+La2O3+B2O3+SiO2+ZrO2+Nb2O5+BaO+Gd2O3.
[0393] According to aspect 62, the glass of any one of aspects 46-61, wherein the glass satisfies the following condition: 4.5 g / cm³ 3 ≤P d ≤5.5g / cm 3 and 1.95≤P n ≤2.07, where P n It is the refractive index parameter, calculated as a mole percent of the components in the glass composition according to the following equation (I):
[0394] P n =1.844+0.0054162*La2O3+0.0031113*TiO2-0.004212*B2O3-0.0035692*SiO2+0.0027887*ZrO2+0.0078026* Nb2O5-0.00012928*CaO+0.00076566*BaO+0.0043601*Y2O3+0.00067408*ZnO+0.0068029*Gd2O3-0.0025106*N a2O+0.0039937*WO3-0.0043208*Al2O3-0.0011666*Li2O+0.0051727*PbO+0.012958*Bi2O3-0.0018753*GeO2- 0.0014084*TeO2+0.0086647*Er2O3+0.0097345*Yb2O3-0.0038734*K2O-0.00041776*SrO-0.0017294*MgO, (I)
[0395] P dIt is a density parameter, calculated as the molar percentage of the components in the glass composition according to the following equation (II):
[0396] P d =4.276+0.058714*La2O3-0.0077783*TiO2-0.023741*B2O3-0.018272*SiO2+0.010913*ZrO2-0.00 14478*CaO+0.023857*BaO+0.033560*Y2O3+0.010174*ZnO+0.082094*Gd2O3-0.008237*Na2O+0.03 5497*WO3-0.031171*Al2O3-0.0080004*Li2O+0.051830*PbO+0.10437*Bi2O3-0.012816*GeO2-0.0 065609*TeO2+0.10060*Er2O3+0.10637*Yb2O3-0.017097*K2O+0.009821*SrO-0.0037906*MgO, (II)
[0397] According to aspect 63, the glass of any one of aspects 46-62, wherein the glass has a density greater than or equal to 4.5 g / cm³. 3 And less than or equal to 5.5 g / cm 3 room temperature density d RT and a refractive index n at 587.56 nm that is greater than or equal to 1.95 and less than or equal to 2.07. d .
[0398] According to aspect 64, a glass of any one of aspects 46-63, wherein the glass has a liquidus temperature T less than or equal to 1260°C. liq .
[0399] According to aspect 65, a glass of any one of aspects 46-64, wherein when cooled in air from 1100°C to 500°C in 2.5 minutes, the glass does not crystallize.
[0400] According to aspect 66, a glass of any one of aspects 46-65, wherein, when the thickness is 10 mm, the glass has a transmittance TX greater than or equal to 70% at a wavelength of 460 nm. 460 nm .
[0401] According to aspect 67, a method for manufacturing an optical element, the method comprising processing glass according to any one of aspects 46-66.
[0402] According to aspect 68, it includes optical elements of glass comprising any one of aspects 46-67.
[0403] Many changes and modifications can be made to the embodiments described above in this disclosure without significantly departing from the spirit and principles of this disclosure. All such changes and modifications are intended to be included herein, fall within the scope of this disclosure, and are protected by the appended claims.
[0404] Within the scope not yet described, different features of various aspects of this disclosure may be combined and used as needed. A particular feature not explicitly shown or described in any aspect of this disclosure is not to be construed as being impermissible, but rather as being done for the sake of brevity and conciseness of description. Thus, various features of different aspects may be mixed and matched as needed to form new aspects, whether or not the new aspects are explicitly disclosed.
Claims
1. A glass comprising multiple components, the glass having the following composition, comprising: Greater than or equal to 0.5 mol% and less than or equal to 29.0 mol% of B2O3, Greater than or equal to 0.0 mol% and less than or equal to 25.2 mol% TiO2, Bi₂O₃, greater than or equal to 0.0 mol% and less than or equal to 20.0 mol%, Greater than or equal to 0.0 mol% and less than or equal to 20.0 mol% TeO2, Greater than or equal to 0.0 mol% and less than or equal to 15.0 mol% of P2O5, Greater than or equal to 0.0 mol% and less than or equal to 10.5 mol% Nb₂O₅ Greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% Al2O3, Greater than or equal to 0.0 mol% and less than or equal to 5.0 mol% of MoO3, Greater than or equal to 0.0 mol% and less than or equal to 4.0 mol% of V₂O₅, Greater than or equal to 0.0 mol% and less than or equal to 2.5 mol% GeO2, Greater than or equal to 0.0 mol% and less than or equal to 2.5 mol% ZnO, Greater than or equal to 0.0 mol% and less than or equal to 1.0 mol% of Ta2O5, Greater than or equal to 95.0 mol% R m O n , Greater than or equal to 0.0 mol% and less than or equal to 29.0 mol% RE m O n , Greater than or equal to 10.0 mol% of SiO2 + B2O3 + P2O5 Less than or equal to 34.0 mol% SiO2 + B2O3 Greater than or equal to 0.3 mol% CaO + SrO + BaO + Y2O3, and Greater than or equal to 0.0 mol% and less than or equal to 25.0 mol% R₂O + RO in, The composition of the components must satisfy the following conditions: Y₂O₃ - Gd₂O₃ [molar percentage] ≥ -2.0, And among them, the glass satisfies the following conditions: 4.0 g / cm 3 ≤ P d ≤ 6.0 g / cm 3 as well as P n - (1.207 + 0.155 P d ) > 0.000, In the formula, P n It is the refractive index parameter, which is calculated from the glass composition in mole percent according to the following equation (I): P n = 1.844 + 0.0054162 La2O3 + 0.0031113 TiO2 - 0.004212 B2O3 -0.0035692 SiO2 + 0.0027887 ZrO2 + 0.0078026 Nb2O5 - 0.00012928 CaO +0.00076566 BaO + 0.0043601 Y2O3 + 0.00067408 ZnO + 0.0068029 Gd2O3 -0.0025106 Na2O + 0.0039937 WO3 - 0.0043208 Al2O3 - 0.0011666 Li2O +0.0051727 PbO + 0.012958 Bi2O3 - 0.0018753 GeO2 - 0.0014084 TeO2 +0.0086647 Er2O3 + 0.0097345 Yb2O3 - 0.0038734 K2O - 0.00041776 SrO -0.0017294 MgO, (I) P d It is a density parameter, calculated as the molar percentage of the components in the glass composition according to the following equation (II): P d (g / cm 3 ) = 4.276 + 0.058714 La2O3 - 0.0077783 TiO2 - 0.023741 B2O3- 0.018272 SiO2 + 0.010913 ZrO2 - 0.0014478 CaO + 0.023857 BaO +0.033560 Y2O3 + 0.010174 ZnO + 0.082094 Gd2O3 - 0.008237 Na2O +0.035497 WO3 - 0.031171 Al2O3 - 0.0080004 Li2O + 0.051830 PbO +0.10437 Bi2O3 - 0.012816 GeO2 - 0.0065609 TeO2 + 0.10060 Er2O3 +0.10637 Yb2O3 - 0.017097 K2O + 0.009821 SrO - 0.0037906 MgO, (II) In the formula, R m O n It is the sum of all oxides, RE m O n It is the sum of rare earth metal oxides, R2O is the sum of monovalent metal oxides, RO is the sum of divalent metal oxides, and the asterisk ( () indicates the multiplication sign.
2. The glass as claimed in claim 1, wherein, The components include: Greater than or equal to 20.0 mol% and less than or equal to 25.2 mol% TiO2, Greater than or equal to 15.0 mol% and less than or equal to 29.0 mol% of La2O3, Greater than or equal to 15.0 mol% and less than or equal to 22.5 mol% of B2O3, Greater than or equal to 5.0 mol% and less than or equal to 20.0 mol% SiO2, Greater than or equal to 4.0 mol% and less than or equal to 9.0 mol% ZrO2, Greater than or equal to 2.5 mol% and less than or equal to 10.0 mol% of Nb₂O₅ BaO, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, Greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% CaO, Greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% of Ga2O3, Greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% of Y₂O₃, and WO3 is greater than or equal to 0.0 mol% and less than or equal to 2.0 mol%.
3. The glass as claimed in claim 1, wherein, The composition of the components satisfies one or more of the following conditions: The sum of the following components is greater than or equal to 99.0 mol%: La₂O₃ + TiO₂ + B₂O₃ + SiO₂ + ZrO₂ + Nb₂O₅ + BaO + Y₂O₃ + CaO + Ga₂O₃ + Gd₂O₃ + ZnO + WO₃ + CeO₂ + SrO + Na₂O + Ta₂O₅ + Al₂O₃. The sum of La2O3 + Y2O3 + Gd2O3 + TiO2 + B2O3 + SiO2 + ZrO2 + Nb2O5 is greater than or equal to 99.0 mol%. The sum of La2O3 + Y2O3 + Gd2O3 + TiO2 + B2O3 + SiO2 + ZrO2 + Nb2O5 + CaO + BaO is greater than or equal to 99.0 mol%, and The sum of La2O3 + TiO2 + B2O3 + SiO2 + ZrO2 + Nb2O5 is greater than or equal to 97.0 mol.
4. The glass as claimed in claim 1, wherein, Glass must meet the following conditions: 4.5 g / cm 3 ≤ P d ≤ 5.5 g / cm 3 as well as 1.95 ≤ P n ≤ 2.07。 5. A glass comprising multiple components, the glass having the following component composition, comprising: Greater than or equal to 1.0 mol% and less than or equal to 40.0 mol% TiO2, Greater than or equal to 1.0 mol% and less than or equal to 40.0 mol% of B2O3, Greater than or equal to 0.0 mol% and less than or equal to 35.0 mol% SiO2, Greater than or equal to 0.0 mol% and less than or equal to 30.0 mol% of La2O3, Greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% ZrO2, Greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% GeO2, Greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% Al2O3, Greater than or equal to 0 mol% and less than or equal to 6.8 mol% Nb₂O₅ Greater than or equal to 0.0 mol% and less than or equal to 6.7 mol% of Y₂O₃ RO, greater than or equal to 0.0 mol% and less than or equal to 25.0 mol%. Greater than or equal to 0.0 mol% and less than or equal to 25.0 mol% R2O, Greater than or equal to 45.3 mol% La2O3 + Y2O3 + Gd2O3 + TiO2 Greater than or equal to 12.1 mol% Nb₂O₅ + ZrO₂, and Optionally includes one or more components selected from the group consisting of: Bi₂O₃, Er₂O₃, Nd₂O₃, WO₃, and Yb₂O₃. in, The composition of the components must satisfy the following conditions: SiO2 + B2O3 - TiO2 [molar%] ≥ 7.05 and B2O3 - SiO2 [molar percentage] ≤ 7.0, And among them, the glass satisfies the following conditions: P ref - (0.196 + 0.0016 (TiO2 - La2O3)) > 0.000 In the formula, P ref It is a refractive power parameter, which is calculated from the glass composition in mol% according to the following equation (III): P ref (cm 3 / g) = 0.201656 + 0.00018225 B2O3 - 0.0010873 BaO - 0.0024853 Bi2O3 - 0.0030326 Er2O3 - 0.0018856 Gd2O3 - 0.0017563 La2O3 - 0.0002505 Na2O + 0.0017526 Nb2O5 - 0.0025472 Nd2O3 - 0.0016439 PbO + 0.000050096 SiO2 + 0.0011794 TiO2 - 0.00072112 WO3 - 0.00079167 Y2O3 - 0.0031015 Yb2O3 - 0.00034209 ZnO, (III) In the formula, RO is the sum of divalent metal oxides, R2O is the sum of monovalent metal oxides, and the symbol ( () indicates the multiplication sign.
6. The glass as claimed in claim 5, wherein, The components include: Greater than or equal to 20.0 mol% and less than or equal to 27.5 mol% TiO2, Greater than or equal to 15.0 mol% and less than or equal to 30.0 mol% of La2O3, Greater than or equal to 15.0 mol% and less than or equal to 22.5 mol% of B2O3, Greater than or equal to 5.0 mol% and less than or equal to 20.0 mol% SiO2, Greater than or equal to 4.0 mol% and less than or equal to 9.0 mol% ZrO2, Greater than or equal to 2.5 mol% and less than or equal to 6.8 mol% Nb₂O₅, BaO, greater than or equal to 0.0 mol% and less than or equal to 10.0 mol%, Greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% CaO, Greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% of Ga2O3, Greater than or equal to 0.0 mol% and less than or equal to 4.0 mol% ZnO, and WO3 is greater than or equal to 0.0 mol% and less than or equal to 2.0 mol%.
7. The glass as claimed in claim 5, wherein, The components include: Greater than or equal to 0.0 mol% and less than or equal to 6.0 mol% R2O + RO.
8. The glass as claimed in claim 5, wherein, The components include: Greater than or equal to 0.0 mol% and less than or equal to 6.5 mol% CaO, and BaO, greater than or equal to 0.0 mol% and less than or equal to 5.5 mol%, and The composition of the components is It contains virtually no ZnO.
9. A glass comprising multiple components, the glass having the following composition, comprising: Greater than or equal to 1.0 mol% and less than or equal to 40.0 mol% TiO2, Greater than or equal to 1.0 mol% and less than or equal to 40.0 mol% of B2O3, Greater than or equal to 0.0 mol% and less than or equal to 35.0 mol% SiO2, Greater than or equal to 0.0 mol% and less than or equal to 30.0 mol% of La2O3, Greater than or equal to 0.0 mol% and less than or equal to 20.0 mol% CaO, Greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% ZrO2, Greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% GeO2, Greater than or equal to 0.0 mol% and less than or equal to 10.0 mol% Al2O3, Greater than or equal to 0 mol% and less than or equal to 6.8 mol% Nb₂O₅ Greater than or equal to 0.0 mol% and less than or equal to 5.5 mol% BaO, Greater than or equal to 0.0 mol% and less than or equal to 4.6 mol% of Y₂O₃ Greater than or equal to 0.0 mol% and less than or equal to 3.5 mol% ZnO, WO3, greater than or equal to 0.0 mol% and less than or equal to 1.0 mol%. RO, greater than or equal to 0.0 mol% and less than or equal to 25.0 mol%. Greater than or equal to 0.0 mol% and less than or equal to 25.0 mol% R2O, Greater than or equal to 45.3 mol% La2O3 + Yb2O3 + Y2O3 + Gd2O3 + TiO2 Greater than or equal to 11.0 mol% Nb₂O₅ + ZrO₂, and Optionally includes one or more components selected from the group consisting of Bi₂O₃, Er₂O₃, and Nd₂O₃. in, The composition of the components must satisfy the following conditions: TiO2 - B2O3 [molar percentage] ≥ -6.0 and TiO2 - La2O3 [molar percentage] ≤ 5.0, And among them, the glass satisfies the following conditions: P ref - (0.199 + 0.0025 (TiO2 - La2O3)) > 0.000 In the formula, P ref It is a refractive power parameter, which is calculated from the glass composition in mol% according to the following equation (III): P ref (cm 3 / g) = 0.201656 + 0.00018225 B2O3 - 0.0010873 BaO - 0.0024853 Bi2O3 - 0.0030326 Er2O3 - 0.0018856 Gd2O3 - 0.0017563 La2O3 - 0.0002505 Na2O + 0.0017526 Nb2O5 - 0.0025472 Nd2O3 - 0.0016439 PbO + 0.000050096 SiO2 + 0.0011794 TiO2 - 0.00072112 WO3 - 0.00079167 Y2O3 - 0.0031015 Yb2O3 - 0.00034209 ZnO, (III) In the formula, RO is the sum of divalent metal oxides, R2O is the sum of monovalent metal oxides, and the symbol ( () indicates a multiplication sign. And the composition of the components satisfies one or more of the following conditions: The sum of the following components is greater than or equal to 99.0 mol%: La₂O₃ + TiO₂ + B₂O₃ + SiO₂ + ZrO₂ + Nb₂O₅ + BaO + Y₂O₃ + CaO + Ga₂O₃ + Gd₂O₃ + ZnO + WO₃ + CeO₂ + SrO + Na₂O + Ta₂O₅ + Al₂O₃. The sum of La2O3 + Y2O3 + Gd2O3 + TiO2 + B2O3 + SiO2 + ZrO2 + Nb2O5 is greater than or equal to 99.0 mol%. The sum of La2O3 + Y2O3 + Gd2O3 + TiO2 + B2O3 + SiO2 + ZrO2 + Nb2O5 + CaO + BaO is greater than or equal to 99.0 mol%, and The sum of La2O3 + TiO2 + B2O3 + SiO2 + ZrO2 + Nb2O5 is greater than or equal to 97.0 mol.
10. The glass as claimed in claim 9, wherein, The composition of the components must satisfy the following conditions: 0.00 ≤ SiO2 / (SiO2 + B2O3) [molar%] ≤ 0.
40.
11. The glass as claimed in claim 9, wherein, The composition of the components must satisfy the following conditions: 0.38 ≤ SiO2 / (SiO2 + B2O3) [molar%] ≤ 0.75.
Citation Information
Patent Citations
Fluorophosphate optical glass, optical preform, element and instrument with a refractive index (nd) of 1.42-1.45 and an Abbe number ([nu]d) of 93-96
TW202012333A
CdO-ThO2-Free, highly refractive optical glass
US4439531A
Method for producing glass, optical glass, glass material for press molding, optical element and methods for producing same
US8661853B2
Optical glass
US8728963B2
High refractivity and high dispersion optical glass, element and instrument
US9487432B2